Insulating adhesive tape
By using a three-layer structure of glass cloth layer, insulating layer and adhesive layer in the insulating adhesive tape, combined with a specific layer thickness and material combination, the problems of low voltage leakage trace and insufficient heat resistance in the prior art are solved. It achieves good leakage resistance and winding processability at high voltages.
Patent Information
- Application Number
- CN202380039650.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-04
- Filing Date
- 2023-05-02
- Publication Date
- 2024-12-20
AI Technical Summary
The existing insulating adhesive tapes are prone to leakage and traces at low voltages, and it is difficult to take into account both heat resistance and winding processability.
Using a three-layer structure composed of a glass cloth layer, an insulating layer and an adhesive layer, the insulating layer and an adhesive layer are both impregnated in the glass cloth layer, and the braid density and material of the glass cloth layer are optimized through a specific layer thickness and material combination. Components, improve insulation and heat resistance.
It achieves good leakage and traceability and winding processability under high voltage conditions, while maintaining high insulation and heat resistance, avoiding the occurrence of leakage and traceability.
Smart Images

Figure CN119173600A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to an insulating adhesive tape. Background Art
[0002] In patent document 1, a flame retardant and heat-resistant adhesive tape is disclosed, which is a support of a heat-resistant adhesive tape having at least one layer formed by a resin composition laminated on at least one side of an impregnated sheet formed by impregnating a resin composition in a non-woven fabric, and the flame retardant and heat-resistant adhesive tape is characterized in that an adhesive layer is provided on at least one side thereof. In addition, in patent document 2, a leakage current tracking resistant pressure-sensitive adhesive tape is disclosed, which has: an electrically insulating film, a composite film including a surface layer and a support film, and a pressure-sensitive adhesive layer. As support films, polyester, polyethylene naphthalate, polyphenylene sulfide, polyetheretherketone, polyimide, insulating tissue paper, polyester non-woven fabric impregnated with epoxy resin, and glass cloth are exemplified. Furthermore, in patent document 3, a non-flammable sheet is disclosed, which is formed by laminating thermoplastic resin layers on both surfaces of a glass cloth via adhesive layers.
[0003] In recent years, electric vehicles (EV), hybrid electric vehicles (HEV), or fuel cell vehicles (FCV), which use electricity from a battery to drive a motor, have become rapidly popular around the world. At present, the voltage of the battery used to drive the motor is 400V, but in order to make the cable thinner or shorten the charging time, it is expected to be boosted to 800V, and then to 1000V, which requires an insulating adhesive tape with heat resistance and high resistance to leakage tracking. In addition, in the context of lightweight and high density, the miniaturization of components is constantly advancing, and the curved surface (radius of curvature) of the winding tape portion becomes smaller, so a thin film, soft, and difficult to peel insulating adhesive tape (hereinafter, abbreviated as winding processability) is required. In addition, although the Comparative Tracking Index (CTI) is determined to be 600 volts, the reverse trend phenomenon that the tracking phenomenon occurs in the low voltage range around 300 volts has become a problem.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2010-76261
[0007] Patent Document 2: U.S. Patent No. 5,501,897
[0008] Patent Document 3: Japanese Patent Application Publication No. 2019-25711 Summary of the invention
[0009] Problems to be solved by the invention
[0010] There is a demand for a technology that can suppress the reverse tendency phenomenon, excel in heat resistance, and suppress insulation failures such as insulation breakdown at low voltage in insulation breakdown voltage tests.
[0011] The present disclosure has been made in view of the above-mentioned circumstances, and an object of the present disclosure is to provide an insulating adhesive tape having excellent heat resistance, good tracking resistance capable of suppressing the reverse tendency phenomenon, high insulation, and good winding processability.
[0012] Technical means of solving problems
[0013] To achieve the above object, an insulating adhesive tape is provided, which is composed of a laminate of at least three layers including an insulating layer, an adhesive layer, and a glass cloth layer between the insulating layer and the adhesive layer, and is a laminate structure including the insulating layer, the glass cloth layer, and the adhesive layer. Specifically, it is as follows.
[0014] [1]: An insulating adhesive tape comprising an insulating layer, an adhesive layer, and a glass cloth layer.
[0015] The glass cloth layer is located between the insulating layer and the adhesive layer, and
[0016] The glass cloth layer is impregnated with at least one of the insulating layer and the adhesive layer.
[0017] [2]: The insulating adhesive tape according to [1], wherein the insulating adhesive tape has a thickness of 30 μm to 200 μm.
[0018] [3]: The insulating adhesive tape according to [1] or [2], wherein the glass cloth layer has a thickness of 10 μm to 50 μm and a weaving density of 10 to 50 strands / 10 mm.
[0019] [4]: The insulating adhesive tape according to any one of [1] to [3], wherein the glass filaments constituting the glass cloth layer have a diameter of 100 μm to 500 μm.
[0020] [5]: The insulating adhesive tape according to any one of [1] to [4], wherein the insulating layer is a hardened material formed by active energy rays.
[0021] [6]: The insulating adhesive tape according to any one of [1] to [5], wherein the insulating layer is a layer formed by curing an acrylic material having a weight average molecular weight of 300 to 15,000.
[0022] [7]: The insulating adhesive tape according to any one of [1] to [6], wherein the insulating layer is formed of a resin mainly composed of polyimide or polyamide having an aromatic ring concentration of 30% by mass or less.
[0023] [8]: The insulating adhesive tape according to any one of [1] to [7], further comprising a thermoplastic resin layer.
[0024] The thermoplastic resin layer is located between the glass cloth layer and the insulating layer, or between the glass cloth layer and the adhesive layer.
[0025] [9]: An insulating adhesive tape according to any one of [1] to [8], wherein the proof tracking index (PTI) measured according to a test based on International Electrotechnical Commission (IEC) 60112, Japanese Industrial Standards (JIS) C2134 or American Society of Testing Materials (ASTM) D3638 is 300 V and 600 V.
[0026]
[10] : The insulating adhesive tape according to any one of [1] to [8], wherein the tracking index (PTI) measured according to a test based on IEC60112, JISC2134 or ASTM D3638 is 300 V, 600 V or 1000 V.
[0027] Effects of the Invention
[0028] According to the present disclosure, it is possible to provide an insulating adhesive tape having excellent tracking resistance, good winding processability even for miniaturized high-voltage parts, and high insulation and heat resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] [ Figure 1A ] is a schematic plan view of the insulating adhesive tape (glass cloth layer) of the first embodiment of the present disclosure.
[0030] [ Figure 1B ]yes Figure 1A IB-IB cut section cross-sectional view.
[0031] [ Figure 2 ] is a schematic side view showing an example of a cross section of an insulating adhesive tape within the scope of implementation.
[0032] [ Figure 3 ] is a schematic side view showing the cross-section of the insulating adhesive tape at different positions according to the first embodiment of the present disclosure.
[0033] [ Figure 4 ] is a schematic side view showing a cross section of an insulating adhesive tape according to a second embodiment of the present disclosure.
[0034] [ Figure 5 ] is a schematic side view showing a cross section of an insulating adhesive tape according to a third embodiment of the present disclosure.
[0035] [ Figure 6 ] is a schematic side view showing a cross section of an insulating adhesive tape according to a fourth embodiment of the present disclosure.
[0036] [ Figure 7 ] is a schematic side view showing a cross section of an insulating adhesive tape according to a fifth embodiment of the present disclosure. DETAILED DESCRIPTION
[0037] Hereinafter, the present embodiment will be described in detail based on the accompanying drawings. The following description of the preferred embodiments is essentially only illustrative and does not limit the present disclosure, its application or its use. In addition, in the present disclosure, insulating adhesive tape, adhesive sheet, adhesive tape and adhesive film are synonymous.
[0038] [Insulating Adhesive Tape]
[0039] The insulating adhesive tape according to the first embodiment will be described using the drawings. Figure 1A It is a plan view of the insulating adhesive tape 1, and for the sake of convenience, the glass cloth layer is shown. Figure 1B yes Figure 1A The cross-section of the band at the IB-IB position. Figure 1B As shown in FIG. 1 , an insulating adhesive tape 1 (hereinafter also abbreviated as tape) includes an insulating layer 12, a glass cloth layer 11, and an adhesive layer 13, wherein the glass cloth layer 11 is located between the insulating layer 12 and the adhesive layer 13. The insulating layer 12 and the adhesive layer 13 are impregnated in the glass cloth layer 11 and are in contact with each other in the glass cloth layer 11. As for the impregnation of the insulating layer 12 and the adhesive layer 13 into the glass cloth layer 11, it is sufficient as long as at least one of the insulating layer 12 and the adhesive layer 13 is impregnated. From the perspective of improving heat resistance, it is preferable to impregnate both the insulating layer 12 and the adhesive layer 13. Each impregnation portion of the insulating layer 12 and the adhesive layer 13 in the insulating adhesive tape 1 will be described in detail. Figure 1BThe dotted line L1 is the outermost boundary line of the insulating layer 12. L3 is the interface where the insulating layer contacts the adhesive layer. L5 is the outermost boundary line of the adhesive layer 13. Here, the distance between L1 and L3 is defined as the thickness of the insulating layer 12, the distance between L3 and L5 is defined as the thickness of the adhesive layer, and the distance between L1 and L5 is defined as the thickness of the tape. In addition, L2 and L4 respectively represent the vertices of the convex parts of the upper surface and the lower surface when the glass cloth layer is observed from a cross section. In this application, the distance between L2 and L4 is defined as the thickness of the glass cloth layer.
[0040] In addition, L1 to L2 of the glass cloth layer that are not impregnated with the insulating layer 12 are defined as insulating non-impregnated layers 12a, and L2 to L3 that are impregnated with the insulating layer 12 are defined as insulating impregnated layers 12b. Similarly, L4 to L5 of the glass cloth layer that are not impregnated with the adhesive layer 13 are defined as adhesive non-impregnated layers 13a, and L3 to L4 that are impregnated with the adhesive layer 13 are defined as adhesive impregnated layers 13b.
[0041] Figure 2 This is a schematic cross-sectional view for explaining a method in which a part of the glass cloth layer has voids. Figure 2 As shown in FIG. 1 , the insulating layer interface L3-1 and L2 on the glass cloth layer impregnation side form an insulating impregnation layer. Similarly, the adhesive layer interface L3-2 and L4 on the glass cloth layer impregnation side form an adhesive layer impregnation layer. A portion of the glass cloth layer 11 may have gaps, but from the perspective of improving insulation, it is preferably as follows: Figure 1B As shown, the insulating layer 12 and the adhesive layer 13 are completely impregnated in the glass cloth layer 11 without any gaps.
[0042] The thickness of the insulating adhesive tape is preferably 30 μm to 200 μm, more preferably 45 μm to 100 μm. When the thickness is 30 μm or more, heat resistance and insulation properties are improved, and when the thickness is 200 μm or less, winding processability is improved.
[0043] The thickness of the glass cloth layer 11 is preferably 10 μm to 50 μm, more preferably 20 μm to 35 μm. Within the preferred range, the insulating adhesive tape has sufficient flexibility while maintaining sufficient strength, and the heat resistance and winding processability are improved.
[0044] The thickness of the insulating layer 12 is preferably 1 μm to 100 μm, more preferably 20 μm to 60 μm. The thickness of the insulating non-impregnated layer 12a is preferably 1 μm to 30 μm, more preferably 5 μm to 15 μm. By the thickness of the insulating layer 12 and the insulating non-impregnated layer 12a being within the preferred range, the tracking resistance and winding processability of the belt can be improved in a well-balanced manner. The ratio of the thickness of the insulating impregnated layer 12b to the thickness of the glass cloth layer is preferably 50% or more, more preferably 70% or more. By being within the preferred range, the gaps in the glass cloth layer 11 are filled with the insulating layer, so the insulation and heat resistance are greatly improved.
[0045] The thickness of the adhesive layer 13 is preferably 5 μm to 100 μm, more preferably 20 μm to 40 μm. The thickness of the adhesive non-impregnated layer 13a is preferably 5 μm to 50 μm, more preferably 20 μm to 35 μm. By making the thickness of the adhesive layer 13 and the adhesive non-impregnated layer 13a within the preferred range, sufficient adhesive performance for the unevenness of various adherends can be obtained.
[0046] The ratio of the thickness of the adhesive impregnation layer 13b to the thickness of the glass cloth layer is preferably 1% or more and less than 50%, and more preferably 1% or more and less than 30%. By being in the above range, the gaps in the glass cloth layer 11 are filled with a large amount of the insulating layer, and the insulation of the tape is improved. By being 1% or more, the adhesion with the glass cloth layer is improved. As described above, it is preferred that the insulating impregnation layer 12b or the adhesive impregnation layer 13b is filled without gaps in the glass cloth layer 11. From the viewpoint of improving the insulation, it is preferred that the sum of the thickness of the insulating impregnation layer 12b and the adhesive impregnation layer 13b is equal to the thickness of the glass cloth layer 11.
[0047] The thickness of each layer of the insulating adhesive tape is evaluated by scanning electron microscope observation (SEM observation) of the tape cross section, and the average value is obtained by measuring 10 random locations in the observation image at a magnification of 300 to 1000 times. Figure 1A The reason is that: it can be confirmed that Figure 3 As shown in the figure, there is no warp or weft, so the thickness of the insulating layer 12 and the adhesive layer 13 can be easily measured. Figure 3As shown, the thickness of the insulating adhesive tape 1 is measured so that the thickness of the insulating non-impregnated layer 12a and the adhesive non-impregnated layer 13a is the smallest from the outermost surface of each of the insulating non-impregnated layer 12a and the adhesive non-impregnated layer 13a to the position where the glass cloth layer can be confirmed, and the remainder after deducting the thickness from the overall tape thickness is defined as the thickness of the glass cloth layer 11. In other words, the thickness including the unevenness of the glass cloth layer 11 is measured so that the thickness is the largest, and the thickness subtracted from the overall tape thickness is defined as the thickness of the insulating non-impregnated layer 12a and the adhesive non-impregnated layer 13a.
[0048] As methods for obtaining the cross-section of the insulating adhesive tape 1, there are methods of separating a target sample frozen by liquid nitrogen or the like (freeze cutting method), a method of cutting the target sample by a sharp tool such as a razor (microtome method), a method of smoothing the cross-section of the target sample cut out by a cutting knife or the like by using abrasive paper, and a method of processing the sample by irradiating an ion beam with a cross section polisher device (ion milling method). A smooth cross-section can be obtained by various methods, but the ion milling method is preferred among these.
[0049] In addition, when it is difficult to distinguish based on color or shape, since the elastic modulus difference between the glass cloth layer 11, the insulating layer 12 and the adhesive layer 13 is large, a scanning probe microscope (sometimes called SPM) can be used to distinguish each layer by showing the size of the elastic modulus as an image on the cross section.
[0050] Furthermore, when the interface between the insulating impregnation layer 12b and the adhesive impregnation layer 13b in the glass cloth layer 11 cannot be fully identified, the adhesive tape is immersed in a container filled with ethyl acetate at 80°C for 12 hours, while the ethyl acetate is made to flow using a stirring member, so that only the adhesive layer is dissolved and removed, and then the layer remaining in the glass cloth layer can be identified as the insulating impregnation layer 12b through cross-sectional observation, which can be combined with the thickness measurement before immersion for identification.
[0051] The 180° peeling adhesion of the adhesive layer in the insulating adhesive tape to the stainless steel plate is preferably 0.1kgf / 20mm to 100kgf / 20mm. If the method of winding around a tubular core material to suppress unexpected peeling and pulling out only the necessary amount for use is considered, it is more preferably 1kgf / 25mm to 50kgf / 25mm in practical use, and further preferably 5kgf / 25mm to 30kgf / 25mm. The adhesion measurement of the product of the present invention refers to the value measured in accordance with JIS Z0237:2009 and using the "cold-rolled stainless steel plate" described in JIS G 4305:2012.
[0052] [Glass cloth layer]
[0053] like Figure 1B As shown in FIG. 1 , the glass cloth layer 11 is a layer located between the insulating layer and the adhesive layer and supports the insulating adhesive tape. The glass cloth layer 11 has a layer partially impregnated with at least one of the insulating layer 12 and the adhesive layer 13. Figure 1B As shown, it has at least an insulating impregnation layer 12b and even an adhesive impregnation layer 13b. Glass cloth is made by weaving glass yarns, and the glass yarns are further formed by bundling glass filaments with small diameters using an adhesive (also called wires). By including such a glass cloth layer 11, heat resistance and winding processability are greatly improved.
[0054] The glass filaments preferably have a diameter of 100 μm to 500 μm, more preferably in the range of 125 μm to 400 μm, and even more preferably in the range of 150 μm to 250 μm. By setting the range, heat resistance and winding processability are improved. The diameter of the glass filaments is the average value of 20 warp and weft yarns when observed perpendicularly to the surface of the glass cloth layer 11 or the insulating adhesive tape using a microscope at a magnification of 50 to 100. The cross-section of the glass filaments is not a perfect circle, and most of them are extreme ellipses. The observed diameter of the glass filaments is consistent with the longest diameter when equivalent to the ellipse. That is, Figure 1B C in is equivalent to the diameter of the glass filament. In the case of difficulty in visual recognition, it is set as the average value of the longest diameters of 20 randomly selected by cross-sectional observation of the tape. By setting it to a preferred range, the strength required for a soft and insulating adhesive tape can be fully satisfied.
[0055] The glass filaments are preferably formed by bundling glass filaments in the range of 10 to 500, more preferably in the range of 30 to 120, and more preferably in the range of 40 to 80. The diameter of the glass filaments is 1 μm to 10 μm, more preferably 3.5 μm to 5.5 μm. The smaller the diameter of the glass filaments or the fewer the number of bundled filaments, the lower the strength of the glass filaments, and the more the flexibility is improved. By setting it to the preferred range, the strength required for the soft and insulating adhesive tape can be fully satisfied. A tape with low flexibility is prone to the undesirable situation that the tape end is easy to peel off during the winding process.
[0056] Glass cloth is a kind of fabric, and its weaving method is not limited. For example, plain weave, twill weave, and segment plain weave can be cited. From the perspective of productivity and uniformity, plain weave is preferred. The weaving density is the average value of the number of warp or weft threads in a 10mm length range of any three parts of the glass cloth surface observed by a microscope at 100 times to 500 times, which is 10 / 10mm to 50 / 10mm, more preferably 15 / 10mm to 40 / 10mm, and further preferably 20 / 10mm to 35 / 10mm. The 10mm length set as the observation range is set in a manner orthogonal to the direction of the observed glass filaments. Regarding the weaving density of the glass cloth layer of the insulating adhesive tape, when the insulating layer or the adhesive layer is transparent, the surface of the tape can be confirmed by microscopic observation. If it cannot be confirmed, it can be confirmed by dissolving and removing the adhesive layer using an organic solvent. If the number of glass fibers increases, the strength of the glass cloth layer increases, but the impregnation of the insulating layer or the adhesive layer decreases, and a large number of voids (pores) are likely to be generated due to insufficient impregnation, and the insulation of the tape deteriorates due to the voids. In the case of a small number of glass fibers, the impregnation of the insulating layer or the adhesive layer into the glass cloth increases, the voids decrease, and the insulation increases, but the tensile strength decreases, so that the tape is prone to breakage during processing. By being in the preferred range, an edge adhesive tape with high insulation and excellent winding processability can be provided.
[0057] When glass nonwoven fabric or glass fiber filler is used between the insulating layer and the adhesive layer instead of glass cloth, the glass nonwoven fabric is not easily impregnated with resin and has poor insulation properties, while the glass fiber filler has poor heat resistance and cannot be used.
[0058] The composition of the glass used in the glass cloth is not particularly limited. For example, by adjusting the composition ratio of silicon oxide to aluminum oxide, magnesium oxide, and boron oxide contained therein, the melting point, dielectric constant, and density can be changed in addition to the strength, and the performance of the present invention can be imparted. For example, when the ratio of silicon oxide to aluminum oxide is increased, the tensile strength is improved, and when the ratio of boron oxide is increased, the density and dielectric constant are reduced.
[0059] The diameter of the glass filaments and the number of bundled fibers can be confirmed by various methods without particular limitation. For example, a cross section of the tape structure of the product of the present invention can be prepared by the above-mentioned method and confirmed.
[0060] The method for measuring the diameter of the glass filaments is to take the average value of the long side and the short side of the cross section of the glass filaments of 10 warp and weft yarns observed at random. In addition, the number of warp yarns and weft yarns can be determined from any three locations of 10 mm square. If it is not possible to visually identify them, it can be confirmed by microscopic observation of the surface of the glass cloth layer after the tape is immersed in an organic solvent, the dissolved adhesive layer is removed, and the surface is exposed. In addition, if the glass cloth layer can be fully visually identified from the tape surface, immersion in an organic solvent is not necessary.
[0061] In addition, when it is difficult to judge based on color or shape, since the elastic modulus difference between glass and resin is large, the cross section can be confirmed using an image showing the magnitude of the elastic modulus using a scanning probe microscope (sometimes called SPM).
[0062] As the glass cloth, commercially available products can be used, for example, E-1037 (thickness: 27 μm) manufactured by Nitto Bosho Co., Ltd. Alternatively, glass cloth produced by a conventionally known method can be used.
[0063] [Insulation layer]
[0064] The insulating layer is a cured product of the insulating composition.
[0065] The insulating layer 12 is located at Figure 1B The insulating adhesive tape 1 is formed on the upper part of the adhesive layer 13 and is subdivided into an insulating non-impregnated layer 12a which is not impregnated in the glass cloth layer 11 and an insulating impregnated layer 12b which is impregnated in the glass cloth layer 11. In addition, when the adhesive layer 13 is impregnated in the entire glass cloth layer, the insulating impregnated layer 12b may not be present.
[0066] The insulating layer 12 imparts tracking resistance, insulation, flexibility, and winding processability to the insulating adhesive tape. The mechanism of tracking is believed to be that when a voltage is applied to the insulating layer as an insulator in a state where there is contamination or dust, and further water, current flows through the insulating layer. When the water evaporates and dries due to Joule heat, the current is concentrated in a part to generate micro discharge, and a part of the insulating layer is decomposed and carbonized.
[0067] Therefore, as a material constituting the insulating layer 12, it is desirable to have four properties: (1) low carbon content (difficult to form a carbonized conductive path), (2) high insulation, (3) high heat resistance, and (4) high flexibility. As for the insulating composition as a precursor, it is desirable to have the property of being easily impregnated into the glass cloth and difficult to form voids in the glass cloth layer 11 in order to suppress the voids in the insulating impregnation layer 12b and the glass cloth layer 11 after curing. In particular, due to the reason (1), the tracking phenomenon cannot be solved by simply improving the insulation.
[0068] As a material having the properties of (1) to (4) above, for example, a cured product formed by active energy rays, or a resin mainly composed of a polyimide having an aromatic ring concentration of 30% by mass or less and a polyamide having an aromatic ring concentration of 30% by mass or less is preferred. From the viewpoint of further improving winding processability, a cured product formed by active energy rays is more preferred.
[0069] <Hardened material formed by active energy rays>
[0070] The cured product formed by active energy rays is a cured product containing a polymerizable compound, which is cured by polymerization of the compound when irradiated with active energy rays such as ultraviolet rays or electron beams, and generally refers to a cured product having ethylenic double bonds (alkenyl groups). Preferably, it is an acrylic material mainly having an acrylate skeleton or a methacrylate skeleton, which is abundant in finished products and relatively inexpensive, and particularly preferably, a urethane acrylate oligomer (sometimes simply referred to as an oligomer) whose flexibility and material strength are easily adjusted.
[0071] The insulating composition for forming the insulating layer 12 preferably contains a component that can be cured by active energy rays as a main component, and is used as a coating liquid by adding a crosslinking agent, an additive, and a solvent so as to facilitate impregnation into the glass cloth and prevent voids from forming during curing.
[0072] The active energy line can be an active energy line having energy quanta in an electromagnetic wave or a charged particle beam, and specifically, ultraviolet rays, electron beams, etc. can be used. Ultraviolet rays, which are easy to operate, are particularly preferred. Ultraviolet rays can be irradiated by a high-pressure mercury lamp, a xenon lamp, etc. The irradiation intensity of ultraviolet rays is preferably 50 mW / cm 2 ~1000mW / cm 2 In addition, the cumulative amount of ultraviolet light is preferably 50mJ / cm 2 ~10000mJ / cm 2 , more preferably 80 mJ / cm 2 ~5000mJ / cm 2 , and preferably 200 mJ / cm 2 ~2000mJ / cm 2 On the other hand, the electron beam irradiation can be performed by an electron beam accelerator or the like. The irradiation dose of the electron beam is preferably about 10 krad to 1000 krad.
[0073] The so-called urethane acrylate oligomer is a reaction product of at least a polyisocyanate and a (meth)acrylate having an active hydrogen group, characterized in that it has a plurality of alkenyl groups at the molecular end. It is usually expanded using polyol compounds or acids and amine compounds. Urethane acrylate oligomers having a plurality of alkenyl groups in the molecule are rapidly hardened by active energy such as ultraviolet rays or electron beams due to the unsaturated carbon bonds derived from acrylates. The hardened material obtained is rigid and has excellent chemical resistance. In the case of crosslinking the free radical polymerizable crosslinking components by ultraviolet rays or the like, a photopolymerization initiator can be used, and a polymerization accelerator can also be used in combination. In the case of crosslinking by electron beams, these do not need to be deployed.
[0074] The weight average molecular weight (Mw) of the urethane acrylate oligomer is preferably 300 to 15,000, more preferably 500 to 5,000, and even more preferably 700 to 2,500. When Mw is 15,000 or less, the impregnation into the glass cloth after coating and drying (uncured and solvent-free state) and the degassing during drying are excellent, the generation of voids inside the glass cloth can be suppressed, and the insulation is improved. When Mw is 300 or more, in addition to suppressing shrinkage during curing, the obtained cured product is not easily brittle, the flexibility can be ensured, and the winding processability is improved.
[0075] The functional group number of the urethane acrylate oligomer is preferably 2 to 5, and more preferably 3 to 4. For example, when 100 parts of a pentafunctional urethane acrylate oligomer are mixed with 100 parts of a trifunctional urethane acrylate oligomer, it can be regarded as a tetrafunctional urethane acrylate oligomer. By being in a preferred range, wrinkles or voids caused by curing shrinkage of the insulating layer can be suppressed, and the insulation is improved due to the high crosslinking density while maintaining flexibility. By being in a more preferred range, the balance of flexibility, strength and insulation is excellent.
[0076] From the viewpoint of suppressing shrinkage and flexibility after curing, the urethane acrylate oligomer preferably has a polyoxyalkylene chain (sometimes also referred to as an EO chain: ethylene oxide chain, a PO chain: propylene oxide chain, an ethylene glycol chain, a propylene glycol chain). The polyoxyalkylene chain can be easily identified by infrared absorption spectrum (IR spectrum). Even if an additive containing a polyoxyalkylene chain is included as an additive, it can be determined that the polyoxyalkylene chain is incorporated into the structure of the urethane acrylate oligomer, i.e., a cured product of the urethane acrylate oligomer having a polyoxyalkylene chain, when the infrared absorption spectrum can be sufficiently identified after immersion in a methyl ethyl ketone (MEK) solution at 25°C for 3 days. In the case where the infrared absorption spectrum is shifted due to steric hindrance, nuclear magnetic resonance (NMR) spectrum and gas chromatography can also be used in combination. In the case of using gas chromatography, the time for the EO chain and the PO chain to pass through the column can be used as a calibration curve to determine the presence or absence.
[0077] Examples of the monofunctional hydroxyl-containing acrylates include 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 2-hydroxy-3-chloropropyl acrylate, N-(2-hydroxyethyl)acrylamide, 2-hydroxy-3-phenoxypropyl acrylate, 2-hydroxy-3-allyloxypropyl acrylate, 2-hydroxy-3-allyloxypropyl acrylate, and 2-acryloyloxyethyl-2-hydroxypropyl phthalate.
[0078] Examples of the monofunctional hydroxyl-containing methacrylate include 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 2-hydroxy-3-chloropropyl methacrylate, 2-hydroxy-3-phenoxypropyl methacrylate, 2-hydroxy-3-allyloxypropyl methacrylate, and 2-methacryloyloxyethyl-2-hydroxypropyl phthalate.
[0079] Examples of the difunctional acrylates include 1,4-butanediol diacrylate, 1,6-hexanediol diacrylate, ethylene glycol diacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, tetraethylene glycol diacrylate, polyethylene glycol 200 diacrylate, polyethylene glycol 300 diacrylate, polyethylene glycol 400 diacrylate, polyethylene glycol 600 diacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, tetrapropylene glycol diacrylate, polypropylene glycol 400 diacrylate, polypropylene glycol 700 diacrylate, neopentyl glycol diacrylate, neopentyl glycol propylene oxide (propylene oxide) oxide, PO) modified diacrylate, hydroxytrimethylol neopentyl glycol diacrylate, hydroxytrimethylol neopentyl glycol caprolactone adduct diacrylate, 1,6-hexanediol bis(2-hydroxy-3-acryloxypropyl) ether, bis(4-acryloxypolyethoxyphenyl) propane, 1,9-nonanediol diacrylate, pentaerythritol diacrylate, pentaerythritol diacrylate monostearate, pentaerythritol diacrylate monobenzoate, bisphenol A diacrylate, ethylene oxide (ethylene oxide, EO) modified bisphenol A diacrylate, PO modified bisphenol A diacrylate, hydrogenated bisphenol A diacrylate, EO modified hydrogenated bisphenol A diacrylate, PO modified hydrogenated bisphenol A diacrylate, bisphenol F diacrylate, EO modified bisphenol F diacrylate, PO modified bisphenol F diacrylate, EO modified tetrabromobisphenol A diacrylate, tricyclodecane dihydroxymethyl diacrylate, isocyanuric acid EO modified diacrylate, ethoxylated isocyanuric acid diacrylate, 2-hydroxy-1,3-diacryloyloxypropane, pentaerythritol diacrylate.
[0080] Examples of the trifunctional acrylates include glycerol PO modified triacrylate, trimethylolpropane triacrylate, trimethylolpropane EO modified triacrylate, trimethylolpropane PO modified triacrylate, isocyanuric acid EO modified triacrylate, ethoxylated isocyanuric acid triacrylate, isocyanuric acid EO modified ε-caprolactone modified triacrylate, 1,3,5-triacryloyl hexahydro-s-triazine, pentaerythritol triacrylate, and dipentaerythritol triacrylate tripropionate. From the viewpoint of flexibility, isocyanuric acid EO modified triacrylate, ethoxylated isocyanuric acid triacrylate, and isocyanuric acid EO modified ε-caprolactone modified triacrylate are preferred.
[0081] Examples of tetrafunctional or higher acrylates include pentaerythritol tetraacrylate, acrylates in which two molecules of ethoxylated isocyanuric acid diacrylate are linked by hexamethylene diisocyanate, dipentaerythritol tetraacrylate, dipentaerythritol pentaacrylate monopropionate, dipentaerythritol hexaacrylate, dipentaerythritol ε-caprolactone-modified hexaacrylate, dipentaerythritol EO-modified hexaacrylate, tetramethylolmethane tetraacrylate, oligoester tetraacrylate, pentaerythritol tetraacrylate, and tri(acryloyloxy)phosphate. From the viewpoint of flexibility, dipentaerythritol EO-modified hexaacrylate is preferred.
[0082] Examples of the difunctional methacrylates include 1,4-butanediol dimethacrylate, 1,6-hexanediol dimethacrylate, ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, polyethylene glycol 200 dimethacrylate, polyethylene glycol 300 dimethacrylate, polyethylene glycol 400 dimethacrylate, polyethylene glycol #600 dimethacrylate, dipropylene glycol dimethacrylate, tripropylene glycol dimethacrylate, tetrapropylene glycol dimethacrylate, polypropylene glycol 400 dimethacrylate, polypropylene glycol 700 dimethacrylate, neopentyl glycol dimethacrylate, neopentyl glycol PO modified dimethacrylate, hydroxypivalate neopentyl glycol dimethacrylate, caprolactone adduct of hydroxypivalate neopentyl glycol dimethacrylate, 1,6-hexanediol bis(2-hydroxy-3 -methacryloyloxypropyl) ether, 1,9-nonanediol dimethacrylate, pentaerythritol dimethacrylate, pentaerythritol dimethacrylate monostearate, pentaerythritol dimethacrylate monobenzoate, 2,2-bis(4-methacryloyloxypolyethoxyphenyl)propane, bisphenol A dimethacrylate, EO-modified bisphenol A dimethacrylate, PO-modified bisphenol A dimethacrylate, hydrogenated bisphenol A dimethacrylate, EO-modified hydrogenated bisphenol A dimethacrylate, PO-modified hydrogenated bisphenol A dimethacrylate, bisphenol F dimethacrylate, EO-modified bisphenol F dimethacrylate, PO-modified bisphenol F dimethacrylate, EO-modified tetrabromobisphenol A dimethacrylate, tricyclodecane dihydroxymethyl dimethacrylate, isocyanuric acid EO-modified dimethacrylate, 2-hydroxy-1,3-dimethacryloyloxypropane, tricyclodecane dimethanol diacrylate.
[0083] Examples of the trifunctional methacrylates include glycerol PO-modified trimethacrylate, trimethylolethane trimethacrylate, trimethylolpropane trimethacrylate, trimethylolpropane EO-modified trimethacrylate, trimethylolpropane PO-modified trimethacrylate, isocyanuric acid EO-modified trimethacrylate, isocyanuric acid EO-modified ε-caprolactone-modified trimethacrylate, 1,3,5-trimethacryloyl hexahydro-s-triazine, pentaerythritol trimethacrylate, and dipentaerythritol trimethacrylate tripropionate. From the viewpoint of flexibility, isocyanuric acid EO-modified trimethacrylate and isocyanuric acid EO-modified ε-caprolactone-modified trimethacrylate are preferred.
[0084] Examples of tetrafunctional or higher methacrylates include pentaerythritol tetramethacrylate, dipentaerythritol pentamethacrylate monopropionate, dipentaerythritol hexamethacrylate, dipentaerythritol ε-caprolactone-modified hexamethacrylate, dipentaerythritol EO-modified hexamethacrylate, tetramethylolmethane tetramethacrylate, oligoester tetramethacrylate, tri(methacryloyloxy)phosphate, and compounds modified with ε-lactone. From the viewpoint of flexibility, dipentaerythritol EO-modified hexamethacrylate is preferred.
[0085] Examples of the diamine include diamines having a linear aliphatic structure such as ethylenediamine, 1,3-propylenediamine, 1,4-butylenediamine, 1,5-pentanediamine, 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,11-undecanediamine, 1,12-dodecanediamine, 1,14-tetradecanediamine, and 1,16-hexadecanediamine. ; diamines having a branched aliphatic structure such as propylenediamine, 1,2-butylenediamine, 1,3-butylenediamine, 2,3-butylenediamine, 2-methyl-1,3-propylenediamine, neopentyldiamine, 1,2-pentanediamine, 3-methyl-1,5-pentanediamine, and 1,8-nonanediamine; diamines having an alicyclic structure such as cyclopropanediamine, cyclohexanediamine, cyclohexanediamine, tricyclodecanediamine, and adamantanediamine.
[0086] In order to promote the photopolymerization of the urethane acrylate oligomer, the protective agent preferably contains a photopolymerization initiator. As specific examples of the photopolymerization initiator, the following substances can be cited. Diethoxyacetophenone, 2-hydroxy-2-methyl-1-phenylpropane-1-one, benzyl methyl ketal, 4-(2-hydroxyethoxy)phenyl-(2-hydroxy-2-propyl)ketone, 1-hydroxycyclohexyl phenyl ketone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinylpropane-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinylphenyl)butane, oligo {2-hydroxy-2-methyl-1-[4-(1-methylvinyl)
[0043] The present invention also includes acetophenones such as 2-hydroxy-1-{4-[4-(2-hydroxy-2-methylpropionyl)benzyl]phenyl}-2-methylpropane-1-one; benzoins such as benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether; phosphines such as 2,4,6-trimethylbenzoin-diphenyl-phosphine oxide and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide; and methyl phenylglyoxylate, but the present invention is not limited to these. More specifically, Irgacure 651, Irgacure 184, Irgacure 1173, Irgacure 500, Irgacure 1000, Irgacure 2959, Irgacure 907, Irgacure 369, Irgacure 379 ... cure) 1700, Irgacure 149, Irgacure 1800, Irgacure 1850, Irgacure 819, Irgacure 784, Irgacure 261, Irgacure OXE-01 (CGI124), CGI242 (BASF), Adeka Optoma Optomer N1414 (Adeka), Adeka Optomer N1717 (Adeka), EsACure 1001M (LAmBerti), bulletins of diazo onium compounds, organic azide compounds, o-quinonediazides, various onium compounds represented by iodonium compounds, metal allene complexes, transition metal complexes containing transition metals such as ruthenium, aluminate compounds, 2,4,5-triarylimidazole dimers, carbon tetrabromide or organic halogen compounds, sulfonium complexes or oxosulfonium complexes, aminoketone oxime ester compounds, etc.
[0087] In addition, as the photopolymerization initiator, a hydrogen abstraction type free radical initiator can be used, and specifically, aromatic ketones such as acetophenone, benzophenone, benzil, Michler's ketone, thioxanthone or anthraquinone can be listed, but it is not limited to these. In the technical field, these compounds are usually used in combination with tertiary amines, and specifically, trimethylamine, triethylamine, tripropylamine, tributylamine, N-methyldiethanolamine, p-dimethylaminophenyl alkyl esters, etc. can be listed, but it is not limited to these.
[0088] Moreover, as a photopolymerization initiator, a photobase generator or a photoacid generator etc. can also be used. These can be used individually by 1 type, and can also use 2 or more types in arbitrary ratios.
[0089] The photobase generator is not particularly limited, and examples thereof include various compounds that generate primary amines, secondary amines, or tertiary amines, such as cobalt amine complexes, o-acyl oximes, carbamic acid derivatives, formamide derivatives, sulfonamides (e.g., N-cyclohexyl-4-methylphenylsulfonamide, etc.), quaternary ammonium salts, toluenesulfonylamines, carbamates (e.g., 2-nitrobenzyl carbamate, 2,5-dinitrobenzylcyclohexyl carbamate, 1,1-dimethyl-2-phenylethyl-N-isopropyl carbamate), amine imide compounds, compounds having an amidine structure, α-aminoacetophenone, etc. The photobase generator may be used alone or in combination of two or more.
[0090] The photoacid generator is not particularly limited, and for example, diazonium salts, iodonium salts, sulfonium salts, phosphonium salts, selenium salts, metallocene complexes, oxathiazole derivatives, s-triazine derivatives, imide compounds, oxime sulfonates, naphthoquinone diazide, sulfonates [1-phenyl-1-(4-methylphenyl)sulfonyloxy-1-benzoylmethane, 1,2,3-trisulfonyloxymethylbenzene, 1,3-dinitro-2-(4-phenylsulfonyloxymethyl)benzene, 1-phenyl-1-(4-methylphenyl)sulfonyloxymethyl-1-hydroxy-1-benzoylmethane, disulfone derivatives (diphenyl disulfone, etc.), benzoin toluenesulfonate, etc.] or Lewis acid salts (triphenylsulfonium antimony hexafluorophosphate, triphenylsulfonium methanesulfonyl, diphenyliodonium hexafluorophosphate).
[0091] As the photopolymerization initiator, among these, acetophenone-based, phosphine oxide-based, and the like can be preferably used.
[0092] The photopolymerization initiator can be used alone or in combination of multiple types, and can be mixed and used arbitrarily according to the properties required for the reaction cured product or the compound cured by active energy rays. The amount of these photopolymerization initiators used is preferably 0.1 to 50 parts by mass relative to 100 parts by mass of the total solid content of the urethane acrylate oligomer.
[0093] Furthermore, a sensitizer may be contained. Examples of the sensitizer include unsaturated ketones represented by chalcone derivatives or dibenzylideneacetone, 1,2-diketone derivatives represented by benzyl or camphorquinone, benzoin derivatives, fluorene derivatives, naphthoquinone derivatives, anthraquinone derivatives, xanthene derivatives, thioxanthene derivatives, xanthone derivatives, thioxanthone derivatives, coumarin derivatives, ketocoumarin derivatives, cyanine derivatives, merocyanine derivatives, polymethine pigments such as oxonol derivatives, acridine derivatives, azine derivatives, thiazine derivatives, oxazine derivatives, indoline derivatives, azulene derivatives, azulenium derivatives, squarylium derivatives, and the like. The compounds include, but are not limited to, acid ylide derivatives, porphyrin derivatives, tetraphenylporphyrin derivatives, triarylmethane derivatives, tetrabenzoporphyrin derivatives, tetrapyrazinoporphyrazine derivatives, phthalocyanine derivatives, tetraazaporphyrazine derivatives, tetraquinoxalinoporphyrazine derivatives, naphthalocyanine derivatives, subphthalocyanine derivatives, pyranium derivatives, thiopyranium derivatives, tetraphylloflavin derivatives, annulene derivatives, spiropyran derivatives, spirooxazine derivatives, thiospiropyran derivatives, metal aromatic complexes, organic ruthenium complexes, Michler's ketone derivatives, and biimidazole derivatives.
[0094] The urethane acrylate oligomer having a polyoxyalkylene chain can be obtained by reacting various polyisocyanates with acrylate or methacrylate having a polyoxyalkylene chain.
[0095] Specific examples of the acrylate or methacrylate having a polyoxyalkylene chain include Blemmer PE-90, Blemmer PE-200, Blemmer PE-350, Blemmer AE-90, Blemmer AE-200, Blemmer AE-350, Blemmer PP-500, Blemmer PP-800, and Blemmer PP-100, which are commercially available products manufactured by NOF Corporation. 00、Blemmer AP-400、Blemmer AP-550、Blemmer AP-800、Blemmer 700PEP-350B、Blemmer 10PEP-550B、Blemmer 55PET-400、Blemmer 30PET-800、Blemmer 55PET-800、Blemmer 30PPT-800、Blemmer 50PPT- 800、Blemmer 70PPT-800、Blemmer PME-100、Blemmer PME-200、Blemmer PME-400、Blemmer PME-1000、Blemmer PME-4000、Blemmer AME-400、Blemmer 50POEP-800B、Blemmer 50AOEP-800B、Blemmer AEP、 Blemmer AET, Blemmer APT, Blemmer PLE, Blemmer ALE, Blemmer PSE, Blemmer ASE, Blemmer PKE, Blemmer AKE, Blemmer PNE, Blemmer ANE, Blemmer PNP, Blemmer ANP, Blemmer PNEP-600;Commercially available products manufactured by Kyoeisha Chemical Co., Ltd. include Light Ester 130MA, Light Ester 041MA, Light Ester MTG, Light Acrylate EC-A, Light Acrylate MTG-A, Light Acrylate 130A, Light Acrylate DPM-A, Light Acrylate P-200A, Light Acrylate NP-4EA, Light Acrylate NP-8EA, Light Acrylate Acrylate) EHDG-A; MA-30, MA-50, MA-100, MA-150, RMA-1120, RMA-564, RMA-568, RMA-506, MPG130-MA, Antox MS-60, MPG-130MA, RMA-150M, RMA-300M, RMA-450M, RA -1020, RA-1120, RA-1820; NK-ester (NK-ESTER) M-20G, M-40G, M-90G, M-230G, AMP-10G, AMP-20G, AMP-60G, AM-90G, LA, which are commercial products manufactured by Shin-Nakamura Chemical Industry Co., Ltd.; Eleminol RS-30, RS-3000, which are commercial products manufactured by Sanyo Chemical Co., Ltd.;
[0096] (Additives, etc.)
[0097] The active energy ray composition can be adjusted to a suitable viscosity by dilution with a solvent, and inorganic fillers, organic fillers, pigments, film-forming aids, flame retardants, light diffusers, plasticizers, solvents, dispersants, wetting agents, thickeners, preservatives, mildewproofing agents, light stabilizers, ultraviolet absorbers, defoaming agents, etc., which are commonly used in coatings, can be added as needed. As the flame retardant, an aluminum phosphate-based flame retardant is preferred.
[0098] As specific examples of inorganic fillers, inorganic microparticles such as oxides, hydroxides, sulfates, carbonates, silicates, etc. containing metals such as magnesium, calcium, barium, zinc, zirconium, molybdenum, silicon, and antimony can be listed. As further detailed specific examples, inorganic particles such as silicon dioxide, silica gel, aluminum oxide, aluminum hydroxide, calcium hydroxide, calcium carbonate, magnesium oxide, magnesium hydroxide, aluminosilicate, talc, mica, glass fiber, glass powder, etc. can be listed. One inorganic filler can be used, or two or more can be used in combination.
[0099] Specific examples of organic fillers include: polymer microparticles such as polytetrafluoroethylene resin, polyethylene resin, polypropylene resin, polymethyl methacrylate resin, polystyrene resin, polyamide resin, melamine resin, guanamine resin, phenol resin, urea resin, silicone resin, methacrylate resin, acrylate resin, or cellulose powder, nitrocellulose powder, wood powder, waste paper powder, shell powder, and starch. The organic filler may be used alone or in combination of two or more.
[0100] The insulating layer 12 may be formed of a resin having at least one selected from the group consisting of the polyimide having an aromatic ring concentration of 30% by mass or less (hereinafter also referred to as "specific polyimide") and the polyamide having an aromatic ring concentration of 30% by mass or less (hereinafter also referred to as "specific polyamide") as a main component. That is, the resin constituting the insulating layer 12 may contain only the specific polyimide as a main component, may contain only the specific polyamide as a main component, or may contain a combination of the specific polyimide and the specific polyamide as a main component.
[0101] (Aromatic ring concentration)
[0102] In this specification, the aromatic ring concentration refers to the content of aromatic rings contained in polyimide or polyamide (hereinafter also referred to as "polymer") (the ratio of the mass of aromatic rings in the raw material of the polymer), and refers to the value obtained by dividing the weight of the portion corresponding to the aromatic ring in the polymer (hereinafter referred to as "aromatic ring skeleton") by the weight of the entire polymer. That is, the aromatic ring concentration is a value calculated based on the composition of the monomer component used as the raw material of the polymer. Specifically, the aromatic ring concentration is calculated by the following formula (1).
[0103] Aromatic ring concentration (mass %) = ["molecular weight of aromatic ring skeleton" x "the number of aromatic ring skeletons contained in the polymer (polyimide or polyamide)"] / [molecular weight of polymer (polyimide or polyamide)] formula (1).
[0104] In addition, the molecular weight of the polymer in formula (1) is the number average molecular weight (Mn). In addition, the so-called aromatic ring skeleton in formula (1) refers to condensed aromatic ring skeletons such as condensed benzene ring skeleton (molecular weight: 76g / mol), condensed naphthalene ring skeleton (molecular weight: 128g / mol), condensed anthracene ring skeleton (molecular weight: 178g / mol), and condensed phenanthrene ring skeleton (molecular weight: 178g / mol). The condensed naphthalene ring skeleton, condensed anthracene ring skeleton, and condensed phenanthrene ring skeleton are each regarded as a condensed aromatic ring skeleton to calculate the aromatic ring concentration.
[0105] From the perspective of achieving improved tracking resistance of the insulating adhesive tape, the aromatic ring concentration is 30% by mass or less, preferably 20% by mass or less. In addition, from the perspective of achieving improved heat resistance of the insulating adhesive tape, the lower limit of the aromatic ring concentration is preferably 5% by mass or more, more preferably 7% by mass or more, and further preferably 8% by mass or more. In other words, from the perspective of obtaining an insulating adhesive tape that takes into account both tracking resistance and heat resistance, the aromatic ring concentration is preferably 5% by mass or more and 30% by mass or less, more preferably 7% by mass or more and 20% by mass or less, and further preferably 8% by mass or more and 20% by mass or less.
[0106] (Functional group concentration (functional group value))
[0107] The functional group concentration (acid value or anhydride value) of the polymer is not particularly limited. With respect to the viewpoint that the weight average molecular weight (Mw) of the polymer is set to the range, it is preferably below 22 mgKOH / g, more preferably below 14 mgKOH / g, further preferably below 11 mgKOH / g, and further preferably below 8 mgKOH / g. In addition, with respect to the viewpoint, its lower limit is preferably above 5 mgKOH / g, more preferably above 6 mgKOH / g. In addition, the functional group concentration can be measured by the method described in the embodiments described later.
[0108] [Polyimide having an aromatic ring concentration of 30% by mass or less]
[0109] Regarding the polyimide having an aromatic ring concentration of 30 mass % or less (specific polyimide), various tetracarboxylic dianhydrides or polyamine compounds may be combined as raw materials if the ratio of the structure derived from the aromatic ring to the entire polymer is 30 mass % or less.
[0110] (Tetracarboxylic dianhydride)
[0111] Regarding tetracarboxylic dianhydride, tetracarboxylic dianhydride having an aliphatic structure or an alicyclic structure is suitable because it is easy to adjust the aromatic ring concentration to 30% by mass or less based on the entire polymer.
[0112] Examples of the tetracarboxylic dianhydride having an aliphatic structure include tetracarboxylic dianhydrides having a chain hydrocarbon structure such as 1,2,3,4-butanetetracarboxylic acid, 1,2,3,4-pentanetetracarboxylic acid, 1,2,4,5-pentanetetracarboxylic acid, 1,2,3,4-hexanetetracarboxylic acid, and 1,2,5,6-hexanetetracarboxylic acid.
[0113] Examples of tetracarboxylic dianhydrides having an alicyclic structure include cyclobutane-1,2,3,4-tetracarboxylic acid, cyclopentane-1,2,3,4-tetracarboxylic acid, cyclohexane-1,2,3,4-tetracarboxylic acid, cyclohexane-1,2,4,5-tetracarboxylic acid, 1-carboxymethyl-2,3,5-cyclopentanetricarboxylic acid, 3-(carboxymethyl)-1,2,4-cyclopentanetricarboxylic acid, acid, TCA), rel-dicyclohexyl-3,3',4,4'-tetracarboxylic acid, tricyclo[4.2.2.02,5]dec-9-ene-3,4,7,8-tetracarboxylic acid, 5-carboxymethylbicyclo[2.2.1]heptane-2,3,6-tricarboxylic acid, bicyclo[2.2.1]heptane-2,3,5,6-tetracarboxylic acid, bicyclo[2.2.2]oct-7-ene-2, 3,6,7-tetracarboxylic acid, bicyclo[3.3.0]octane-2,4,6,7-tetracarboxylic acid, 7,8-diphenylbicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic acid, 4,8-diphenyl-1,5-diazabicyclooctane-2,3,6,7-tetracarboxylic acid, 9-oxatricyclo[4.2.1.02,5]nonane-3,4,7,8-tetracarboxylic acid, 9, Cyclic tetracarboxylic acids, bicyclic tetracarboxylic acids, tricyclic tetracarboxylic acids such as 14-dioxopentacyclo[8.2.11,11.14,7.02,10.03,8]tetradecane-5,6,12,13-tetracarboxylic acid; spirocyclic tetracarboxylic acids such as 2,8-dioxaspiro[4.5]decane-1,3,7,9-tetraone; tetracarboxylic dianhydrides having an alicyclic hydrocarbon structure such as 1,3,3a,4,5,9b-hexahydro-5(tetrahydro-2,5-dioxo-3-furanyl)naphtho[1,2-c]furan-1,3-dione (TDA).
[0114] As tetracarboxylic dianhydride other than the aliphatic structure or alicyclic structure, if the aromatic ring concentration can be adjusted to 30% by mass or less, tetracarboxylic dianhydride with an aromatic structure can also be used. As specific examples, pyromellitic dianhydride (PMDA), 3,3',4,4'-biphenyl tetracarboxylic dianhydride (BPDA), 1,2,3,4-benzene tetracarboxylic dianhydride, 1,4,5,8-naphthalene tetracarboxylic dianhydride, 2,3,6,7-naphthalene tetracarboxylic dianhydride, diphthalic dianhydride can be listed. Among these, PMDA and BPDA are preferred.
[0115] The tetracarboxylic dianhydride having an aliphatic structure, an alicyclic structure or an aromatic structure can be used alone or in combination of two or more. In addition, the monomer examples can also be suitably substituted. As substituents, alkyl, halogen atoms, nitro, cyano can be exemplified. In addition, tetracarboxylic acid derivatives such as tetracarboxylic acids or tetracarboxylic acid diesters having the same structure can also be used to replace the tetracarboxylic dianhydride.
[0116] (Polyamine compounds)
[0117] As with the tetracarboxylic dianhydride, polyamine compounds having an aliphatic structure or an alicyclic structure are suitable because the aromatic ring concentration relative to the entire polymer can be easily adjusted to 30% by mass or less. Among them, polyamine compounds having a dimer structure, namely dimerdiamine (DDA), are preferred.
[0118] As the dimer diamine, a compound obtained by converting the carboxyl group of a dimer acid into an amino group can be used. A dimer acid is a polyacid compound having a dimer structure and is a dimer of a fatty acid (hereinafter referred to as a "fatty acid dimer").
[0119] The fatty acid dimer is preferably a compound having 20 to 60 carbon atoms, more preferably a compound having 24 to 56 carbon atoms, further preferably a compound having 28 to 48 carbon atoms, and further preferably a compound having 36 to 44 carbon atoms. The fatty acid dimer is preferably a dicarboxylic acid compound having a branched structure obtained by subjecting a fatty acid to a Diels-Alder reaction. The fatty acid is preferably an unsaturated fatty acid having 10 to 30 carbon atoms, and more preferably an unsaturated fatty acid having 10 to 24 carbon atoms. The unsaturated fatty acid has one or more carbon-carbon double bonds or carbon-carbon triple bonds. Specific examples of the fatty acid include natural fatty acids such as soybean oil fatty acids, tall oil fatty acids, and rapeseed oil fatty acids, as well as oleic acid, linolenic acid, linolenic acid, erucic acid, etc., which are refined from these. The branched structure is preferably a fatty chain structure and a ring structure, and more preferably a ring structure. The ring structure is preferably one or more aromatic rings and alicyclic structures, and more preferably one or more alicyclic structures. The alicyclic structure may have one double bond in the ring or may not have a double bond.
[0120] When synthesizing fatty acid dimers, in addition to generating fatty acid dimers, trimers of fatty acids are also generated or tetramers are generated as appropriate. Therefore, the polyacid compound containing a dimer skeleton is a mixture of fatty acids containing not only fatty acid dimers as main components but also fatty acid trimers, etc., as raw materials as appropriate. The content of fatty acid dimers in dimer acid is preferably 70% by mass or more, more preferably 90% by mass or more, and further preferably 95% by mass or more.
[0121] Regarding dimer acid, since unsaturated fatty acids are used in the raw materials, unsaturated bonds sometimes remain. In such cases, hydrogenation (also referred to as hydrogenation reaction) can be performed to suppress the number of unsaturated bonds. Thus, the reaction stability during the synthesis of the specific polyimide is improved, and the heat resistance of the insulating adhesive tape containing the specific polyimide is improved.
[0122] Examples of commercially available dimer acids include "Pripol 1004", "Pripol 1006", "Pripol 1009", "Pripol 1013", "Pripol 1015", "Pripol 1017", "Pripol 1022", "Pripol 1025", and "Pripol 1040" manufactured by Croda Japan; and "Pripol 1040" manufactured by BASF Japan. "Empol 1008", "Empol 1012", "Empol 1016", "Empol 1026", "Empol 1028", "Empol 1043", "Empol 1061", and "Empol 1062" manufactured by Empol Japan. These may be used alone or in combination of two or more.
[0123] The dimer diamine is preferably a compound having 20 to 60 carbon atoms, more preferably a compound having 24 to 56 carbon atoms, further preferably a compound having 28 to 48 carbon atoms, and further preferably a compound having 36 to 44 carbon atoms. From the viewpoint of easy availability, the dimer diamine having the above carbon atoms is preferred.
[0124] Examples of commercially available products of dimer diamine (DDA) include "PRIAMINE 1071", "PRIAMINE 1073", "PRIAMINE 1074", and "PRIAMINE 1075" manufactured by Croda Japan, and "Versamine 551" manufactured by BASF Japan. These may be used alone or in combination of two or more.
[0125] In addition, the structure of the polyacid compound having a dimer structure for obtaining the dimer diamine can take multiple forms in terms of the synthesis process, and is not limited to the above structure.
[0126] The polyamine compounds other than the dimer diamine (hereinafter also referred to as "other diamines") are not particularly limited, and examples thereof include diamine compounds having an aliphatic structure (a chain hydrocarbon structure and / or an alicyclic hydrocarbon structure that may contain an unsaturated bond) and an aromatic structure (the aromatic ring and the above structures may be arbitrarily combined) that may have a substituent.
[0127] The above-mentioned dimer structure (dimer diamine) and polyamine compounds other than dimer diamine (other diamines) may be used alone or in combination of two or more.
[0128] (Other single bodies)
[0129] As the raw material of the resin component constituting the insulating layer 12, monomers other than those mentioned above may be used within the scope that does not hinder the purpose of the present invention. For example, a polyamine compound having three or more amino groups may be used. Examples of the polyamine compound having three or more amino groups include 1,2,4-triaminobenzene and 3,4,4'-triaminodiphenyl ether.
[0130] (Crosslinking agent)
[0131] The specific polyimide is crosslinked by reacting with a crosslinking agent, thereby improving the heat resistance of the insulating layer 12. Therefore, it is preferable that a crosslinking agent is contained in the monomer component used as a raw material of the specific polyimide.
[0132] Examples of the crosslinking agent include compounds having two or more reactive functional groups in one molecule and capable of forming a crosslinked structure, and specific examples include epoxy compounds, cyanate compounds, isocyanate group-containing compounds, chelating agent compounds, and carbodiimide group-containing compounds.
[0133] The epoxy compound is a compound having two or more epoxy groups in one molecule, and existing compounds can be used.
[0134] Examples of epoxy compounds include bisphenol A epoxy resins, bisphenol F epoxy resins, biphenyl epoxy resins, novolac epoxy resins, dicyclopentadiene epoxy resins, polyfunctional phenol epoxy resins, naphthalene epoxy resins, aralkyl-modified epoxy resins, alicyclic and alcohol glycidyl ethers, alicyclic and alcohol glycidyl amines (e.g., "TETRAD C" and "TETRAD X" manufactured by Mitsubishi Gas Chemical Co., Ltd.), and alicyclic and alcohol glycidyl ester resins.
[0135] The crosslinking agent may be a low molecular compound or a high molecular compound. In addition, the crosslinking agent may be a compound that the crosslinking agent itself exhibits thermosetting properties, or a compound that the crosslinking agent and a specific polyimide are crosslinked. The crosslinking agent may be used alone or in combination of two or more.
[0136] (Functional Group)
[0137] The specific polyimide preferably has a functional group because it can improve heat resistance by crosslinking through reaction with the crosslinking agent.
[0138] As functional groups, carboxyl, amino, hydroxyl, anhydride groups can be exemplified. These can be functional groups derived from monomers used as raw materials for specific polyimides, and functional groups can also be introduced as modified products after obtaining polymers. In addition to the mode of being present at the end of the polymer, there is also a mode of having a functional group in a side group and / or a side chain. As a suitable example, a mode of having a functional group such as a carboxyl, anhydride or amino group at the end of the polymer can be exemplified. In addition, a mode of having at least one functional group such as a carboxyl, amino, hydroxyl group in a side group or a side chain can be exemplified.
[0139] In the case of having hydroxyl as a functional group, phenolic hydroxyl is suitable. By having a phenolic hydroxyl, a cross-linked structure with a cross-linking agent can be constructed to form a tough insulating layer. Phenolic hydroxyl can be easily introduced by using a polyacid compound with a phenolic hydroxyl and / or a polyamine compound with a phenolic hydroxyl. It is preferred that the aromatic ring of the phenolic hydroxyl is contained in the main chain skeleton. In addition, it is preferred to use a polyacid compound with a phenolic hydroxyl.
[0140] (catalyst)
[0141] When the specific polyimide is reacted with the crosslinking agent to crosslink, a catalyst may be used. Examples of the catalyst include: aliphatic tertiary amines such as triethylamine; aromatic tertiary amines such as dimethylaniline; heterocyclic tertiary amines such as pyridine, picoline, and isoquinoline; phosphorus compounds, etc. Specifically, examples include: 1,8-diazabicyclo[5,4,0]-undecene-7 (1,8-Diazabicyclo[5,4,0]-undecene-7, DBU), triphenylphosphine (triphenylphosphine, TPP), etc.
[0142] [Method for producing a polyimide having an aromatic ring concentration of 30% by mass or less]
[0143] The polyimide (specific polyimide) having an aromatic ring concentration of 30% by mass or less can be produced by various conventional methods. As a specific example, a method in which a polyamic acid resin or a polyamic acid ester resin as a polyimide precursor is cyclized by heating to convert the polyimide into an imide group can be cited.
[0144] The synthesis method of the polyamic acid resin can be, for example, a method of reacting tetracarboxylic dianhydride with diamine. Specifically, monomer components including tetracarboxylic dianhydride and diamine are dissolved in a solvent and polymerized by stirring at a temperature of, for example, 60°C to 120°C for 0.1 to 2 hours, thereby producing a polyamic acid resin as a polyimide precursor.
[0145] The synthesis method of polyamic acid ester resin includes, for example, a method of obtaining a diester from tetracarboxylic acid dianhydride and alcohol, and then reacting the diester with diamine in the presence of a condensing agent; a method of obtaining a diester from tetracarboxylic acid dianhydride and alcohol, and then chlorinating the remaining dicarboxylic acid and reacting it with diamine. In this way, a polyamic acid ester resin as a polyimide precursor can be produced.
[0146] Examples of organic solvents used in polymerization include N-methyl-2-pyrrolidone (NMP), 2-butanone, dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N,N-diethylacetamide, hexamethylphosphoramide, N-methylcaprolactam, dimethyl sulfate, cyclohexanone, dioxane, tetrahydrofuran, dimethyl ether, trimethyl ether, and cresol. The organic solvents may be used alone or in combination of two or more. In addition, the organic solvents may be used in combination with aromatic hydrocarbons such as xylene and toluene.
[0147] The method of cyclizing the polyimide precursor by heating to convert it into an imide group, that is, the method of imidizing the polyimide precursor to obtain the polyimide resin is not particularly limited, and an example thereof includes heating in a solvent at a temperature of 80° C. to 400° C. for 0.5 to 50 hours. At this time, a catalyst and / or a dehydrating agent may be used as needed.
[0148] Examples of the catalyst include aliphatic tertiary amines such as triethylamine, aromatic tertiary amines such as dimethylaniline, heterocyclic tertiary amines such as pyridine, picoline, and isoquinoline, and examples of the dehydrating agent include aliphatic anhydrides such as acetic anhydride, and aromatic anhydrides such as benzoic anhydride.
[0149] The imidization rate (imide ring formation rate) of the specific polyimide is not particularly limited, but is preferably 80% or more, more preferably 90% or more, and further preferably 95% to 100% from the viewpoint of forming an insulating layer that imparts excellent tracking resistance to the substrate layer. The imidization rate can be determined by NMR or IR analysis, etc.
[0150] [Polyamide having an aromatic ring concentration of 30% by mass or less]
[0151] Aromatic ring concentration is 30% by mass or less polyamide (specific polyamide) is a polymer containing repeating structural units containing amide groups. Specifically, specific polyamide is a polymer of polyacid compounds, polyamine compounds, other monomers as needed, or a modified body formed by modifying the polymer. Here, the so-called modified body is a derivative obtained by converting a part of the molecular structure of the polymer (for example, conversion of functional groups, substitution with other compounds, or addition of other compounds). Regarding specific polyamide, if the proportion of the structure derived from the aromatic ring relative to the whole polymer is 30% by mass or less, various polyacid compounds or polyamine compounds can be combined as raw materials.
[0152] In order to adjust the aromatic ring concentration to 30% by mass or less, it is preferred to introduce a dimer structure into the polyamide resin. When introducing a dimer structure into the polyamide resin, it is sufficient to use a monomer having a dimer structure. As a polyacid compound having a dimer structure, a dimer acid is suitable. Dimer acids can include the same dimer acids as the fatty acid dimers exemplified in the specific polyimide. In addition, as a polyamine compound having a dimer structure, dimer diamines are suitable. Dimer diamines can include the same dimer diamines as the dimer diamines exemplified in the specific polyimide.
[0153] (Polyacid Compound)
[0154] The polyacid compound is a carboxylic acid having a dibasic acid or higher. A part of the polyacid compound may be an acid anhydride. Examples of the polyacid compound include the dimer acid and other polyacid compounds.
[0155] The other polybasic acid compound is a polybasic acid compound other than the dimer acid, and is a difunctional or higher functional compound.
[0156] Examples of the dibasic acid compound include aromatic dibasic acids such as phthalic acid, isophthalic acid, terephthalic acid (TPA), 1,4-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, benzophenone-4,4'-dicarboxylic acid, and 4,4'-biphenyl dicarboxylic acid; aliphatic dibasic acids such as oxalic acid, malonic acid, methylmalonic acid, succinic acid, glutaric acid, adipic acid, maleic acid, fumaric acid, malic acid, tartaric acid, thiomalic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, dodecanedioic acid, hexadecanedioic acid, and diglycolic acid; and alicyclic dibasic acids such as 1,3-cyclohexane dicarboxylic acid, 1,4-cyclohexane dicarboxylic acid, and 1,3-cyclopentane dicarboxylic acid. Among the dibasic acid compounds, isophthalic acid, terephthalic acid (TPA) and 1,4-cyclohexane dicarboxylic acid are preferred.
[0157] Examples of the trifunctional or higher polybasic acid compound include trimellitic acid, hydrogenated trimellitic acid, pyromellitic acid, hydrogenated pyromellitic acid, trimesic acid, and 1,4,5,8-naphthalenetetracarboxylic acid.
[0158] In addition, as a suitable example of other polyacid compounds, polyacid compounds having phenolic hydroxyl groups can be cited. By using polyacid compounds having phenolic hydroxyl groups, a tough insulating layer can be formed. The polyacid compound having phenolic hydroxyl groups is a compound having phenolic hydroxyl groups and having two or more acidic functional groups. The acidic functional groups can be, for example, carboxyl groups.
[0159] Examples of the polyacid compound having a phenolic hydroxyl group include monohydroxyisophthalic acids such as 2-hydroxyisophthalic acid, 4-hydroxyisophthalic acid, and 5-hydroxyisophthalic acid (5-HIP); dihydroxyisophthalic acids such as 2,5-dihydroxyisophthalic acid, 2,4-dihydroxyisophthalic acid, and 4,6-dihydroxyisophthalic acid; monohydroxyterephthalic acids such as 2-hydroxyterephthalic acid; dihydroxyterephthalic acids such as 2,3-dihydroxyterephthalic acid and 2,6-dihydroxyterephthalic acid; hydroxyphthalic acids such as 3-hydroxyphthalic acid and 4-hydroxyphthalic acid; and dihydroxyphthalic acids such as 3,4-dihydroxyphthalic acid, 3,5-dihydroxyphthalic acid, 4,5-dihydroxyphthalic acid, and 3,6-dihydroxyphthalic acid. Among these, 5-hydroxyisophthalic acid (5-HIP) is preferred in terms of copolymerizability, availability, etc. In addition, regarding the polyacid compound having a phenolic hydroxyl group, the carboxyl group of the above-exemplified compound may form an anhydride group, or the carboxyl group may form an ester.
[0160] The dimer acid and other polyacid compounds exemplified as the polyacid compound may be used alone or in combination of two or more.
[0161] (Crosslinking agent)
[0162] The specific polyamide can be cross-linked by reacting with a cross-linking agent to improve the heat resistance of the insulating layer. Therefore, it is preferred that the monomer component used as the raw material of the specific polyamide contains a cross-linking agent. The cross-linking agent can be the same as the cross-linking agent exemplified in the specific polyimide.
[0163] (Functional Group)
[0164] The specific polyamide preferably has a functional group because it can improve heat resistance by crosslinking through reaction with the crosslinking agent. Examples of the functional group include the same functional groups as those exemplified in the specific polyimide, and a phenolic hydroxyl group is preferred.
[0165] (other)
[0166] The specific polyamide may be a polyamideimide partially having an imide group or a polyamide ester partially having an ester group, within a range not inhibiting the purpose of the present invention.
[0167] [Method for producing polyamide having an aromatic ring concentration of 30% by mass or less]
[0168] The polyamide (specific polyamide) having an aromatic ring concentration of 30% by mass or less can be produced by various existing methods. As a specific example, melt polymerization, interfacial polymerization, solution polymerization, bulk polymerization, solid phase polymerization, or a combination thereof can be used for synthesis. Among these, solution polymerization is preferred.
[0169] The polymer of the specific polyamide can be carried out using monomer components containing polyacid compounds, polyamine compounds, and other monomers as needed, in the presence or absence of a catalyst. For example, a flask filled with nitrogen is charged with a predetermined amount of dimer acid, other acid monomers, dimer diamine, other amine monomers and ion exchange water, and heated and stirred at 20°C to 100°C, thereby uniformly dissolving and dispersing. Thereafter, while removing the ion exchange water and the water generated by the reaction, the temperature is slowly raised to 230°C, and after reaching 230°C, the pressure is gradually reduced to about 15mmHg, and the state is maintained for about 1 hour, thereby obtaining a specific polyamide. The heating temperature is, for example, 150°C to 300°C. The heating time is about 1 hour to 24 hours. In order to promote the synthesis reaction, it is preferably to carry out a dehydration or dealcoholization reaction. In addition, in order to avoid coloring and decomposition reactions caused by high temperatures, it is preferably to react under reduced pressure at 180°C to 270°C.
[0170] The specific polyimide and the specific polyamide may be used alone or in combination of two or more thereof. Of the specific polyimide and the specific polyamide, the specific polyimide is more preferred from the viewpoint of obtaining an insulating adhesive tape having both tracking resistance and heat resistance.
[0171] The resin component constituting the insulating layer may contain other resins other than the specific polyimide and the specific polyamide within the range not hindering the purpose of the present invention. Examples of other resins that can be used together with the specific polyimide and / or the specific polyamide include fluororesins and the like.
[0172] The insulating composition containing the specific polyimide and / or specific polyamide can be adjusted to a suitable viscosity by the crosslinking agent or solvent, and inorganic fillers, organic fillers, pigments, film-forming aids, flame retardants, light diffusers, plasticizers, dispersants, wetting agents, tackifiers, preservatives, mildewproofing agents, light stabilizers, ultraviolet absorbers, defoaming agents, etc. used in general coatings can be added as needed. As the flame retardant, aluminum phosphate-based flame retardants are preferred.
[0173] [Adhesive layer]
[0174] The adhesive layer is a layer formed by applying an adhesive composition and curing it, and is a layer for imparting adhesiveness. Figure 1B As shown, the insulating layer 12 of the insulating adhesive tape 1 constitutes another outermost layer, and is subdivided into an adhesive impregnated layer 13b impregnated in the glass cloth layer 11, and an adhesive non-impregnated layer 13a not impregnated in the glass cloth layer 11. In addition, when the insulating layer 12 is impregnated in the entire glass cloth layer, the adhesive impregnated layer 13b may not exist.
[0175] The adhesive composition for forming the adhesive layer mainly comprises an adhesive, and as the adhesive, for example, can be enumerated: acrylic adhesive, silicone adhesive, rubber adhesive, urethane adhesive. These can be used separately, respectively, or two or more can be used in combination. Among these, with respect to the viewpoint of heat resistance, silicone adhesive is preferably used, and with respect to the viewpoints such as the ease of adjustment of the subtlety of the adhesive force of heat resistance and stability over time, no silicone contamination, and resistance to insulating varnish characteristics, etc., acrylic adhesive is further preferably used. By adding a cross-linking agent, additives, etc. to the adhesive as needed and fully mixing, an adhesive composition can be obtained. In addition, the viscosity suitable for coating can be adjusted by utilizing the dilution of a solvent.
[0176] As the silicone-based adhesive, a known material can be used as the silicone resin. Specifically, a material having R 3 SiO 0.5 (here, R represents a substituted or unsubstituted monovalent hydrocarbon group) and an organopolysiloxane part of an SiO2 unit is dehydrated and condensed on an organopolysiloxane having silanol groups at both ends of the molecular chain. These can be obtained as silicone adhesives KR-101-10, KR-120, KR-130, and X-40-3068 (all manufactured by Shin-Etsu Chemical Co., Ltd.). The curing method of silicone adhesives is generally a curing method using peroxides such as benzoyl peroxide, and a curing method using a platinum catalyst and an organopolysiloxane having a Si-H bond. Either method can be used, and a combination of the two can also be used.
[0177] The acrylic adhesive preferably contains a (meth)acrylate polymer. In other words, the adhesive composition used as the raw material of the acrylic adhesive contains a (meth)acrylate polymer. In addition, in this specification, the so-called (meth)acrylic acid refers to acrylic acid and / or methacrylic acid. In addition, in this specification, the concept of "copolymer" is also included in "polymer".
[0178] ((Meth)acrylate polymer)
[0179] The (meth)acrylate polymer can show preferred adhesiveness by containing a (meth)acrylate alkyl ester having an alkyl group with a carbon number of 1 to 20 as a monomer unit constituting the polymer. Examples of the (meth)acrylate alkyl ester include: methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate [BA, BMA], n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate [2-EHA, 2-EHMA], isooctyl (meth)acrylate, n-decyl (meth)acrylate, n-dodecyl (meth)acrylate, myristyl (meth)acrylate, palmityl (meth)acrylate, and stearyl (meth)acrylate. These can be used alone or in combination of two or more. Among these, from the viewpoint of improving the adhesiveness of the insulating adhesive tape, (meth)acrylates having an alkyl group with 1 to 8 carbon atoms are preferred, n-butyl (meth)acrylate [BA, BMA] and 2-ethylhexyl (meth)acrylate [2-EHA, 2-EHMA] are more preferred, and n-butyl acrylate [BA] and 2-ethylhexyl acrylate [2-EHA] are still more preferred.
[0180] The (meth)acrylate polymer preferably contains 50% by mass or more of an alkyl (meth)acrylate having an alkyl group with a carbon number of 1 to 20 as a monomer unit constituting the polymer, more preferably contains 60% by mass or more, and further preferably contains 70% by mass or more. By containing 50% by mass or more of the alkyl (meth)acrylate, the (meth)acrylate polymer can exert suitable adhesion. In addition, the (meth)acrylate polymer preferably contains 90% by mass or less of an alkyl (meth)acrylate having an alkyl group with a carbon number of 1 to 20 as a monomer unit constituting the polymer, more preferably contains 80% or less. By containing 90% by mass or less of the alkyl (meth)acrylate, other monomer components can be introduced into the (meth)acrylate polymer in a suitable amount.
[0181] In order to impart adhesive properties and cohesive strength, the (meth)acrylate polymer is preferably a copolymer obtained by copolymerizing a (meth)acrylate alkyl ester having an alkyl group with 1 to 20 carbon atoms as the main component of the polymer and a monomer containing a reactive functional group (hereinafter referred to as "reactive functional group-containing monomer").
[0182] Examples of monomers containing reactive functional groups include monomers having a carboxyl group in the molecule (hereinafter referred to as "carboxyl group-containing monomers"), monomers having a hydroxyl group in the molecule (hereinafter referred to as "hydroxyl group-containing monomers"), monomers having an amino group in the molecule (hereinafter referred to as "amino group-containing monomers"), etc. These monomers may be used alone or in combination of two or more.
[0183] Examples of carboxyl-containing monomers include ethylenically unsaturated carboxylic acids such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, itaconic acid, and citraconic acid. These may be used alone or in combination of two or more. Of these, acrylic acid is preferred. Acrylic acid provides a more excellent effect.
[0184] The (meth)acrylate polymer preferably contains 0.5% by mass or more of a carboxyl-containing monomer as a monomer unit constituting the polymer, more preferably 1% by mass or more, and further preferably 3% by mass or more. In addition, the (meth)acrylate polymer preferably contains 30% by mass or less of a carboxyl-containing monomer as a monomer unit constituting the polymer, more preferably 25% by mass or less, and further preferably 20% by mass or less.
[0185] Examples of the hydroxyl group-containing monomer include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate. These may be used alone or in combination of two or more.
[0186] Examples of the amino group-containing monomer include aminoethyl (meth)acrylate and n-butylaminoethyl (meth)acrylate, which may be used alone or in combination of two or more.
[0187] The polymerization method of the (meth)acrylate polymer may be a random copolymer or a block copolymer.
[0188] From the viewpoint of improving the heat resistance, solvent resistance, adhesion characteristics and durability of the adhesive, the weight average molecular weight of the (meth) acrylate polymer is preferably 200,000 or more, more preferably 300,000 or more, and further preferably 400,000 or more, and further more preferably 500,000 or more. In addition, from the viewpoint of improving the adhesion of the obtained adhesive, its upper limit is preferably 2.5 million, more preferably 2 million, further preferably 1.5 million, and further more preferably 1.2 million. In addition, the weight average molecular weight in this specification is a value converted from standard polystyrene measured by gel permeation chromatography (gel permeation chromatography, GPC) method.
[0189] (Crosslinking agent)
[0190] As a crosslinking agent, as long as it reacts with the reactive functional group possessed by the (meth) acrylate polymer, for example, isocyanate crosslinking agents, epoxy crosslinking agents, amine crosslinking agents, melamine crosslinking agents, aziridine crosslinking agents, hydrazine crosslinking agents, aldehyde crosslinking agents, oxazoline crosslinking agents, metal alkoxide crosslinking agents, metal chelate crosslinking agents, metal salt crosslinking agents, and ammonium salt crosslinking agents can be listed. These can be used alone or in combination of two or more. Among these, isocyanate crosslinking agents are preferred. In the above case, the (meth) acrylate polymer preferably contains at least one or more monomers containing carboxyl groups or hydroxyl groups as monomer units constituting the polymer. The interfacial strength of the adhesive obtained by combining with the isocyanate crosslinking agent and the glass cloth layer is greatly improved. As a result, a tape (cellophane tape-shaped wrap) can be directly produced as a wrap without using a release liner, which is beneficial to processability and peelability from the back.
[0191] Isocyanate crosslinking agents at least include polyisocyanate compounds. As polyisocyanate compounds, for example, aromatic polyisocyanates such as toluene diisocyanate, diphenylmethane diisocyanate, and xylylene diisocyanate; aliphatic polyisocyanates such as hexamethylene diisocyanate; alicyclic polyisocyanates such as isophorone diisocyanate and hydrogenated diphenylmethane diisocyanate, and these biuret bodies, isocyanurate bodies, and reaction products of low molecular weight compounds containing active hydrogen such as ethylene glycol, propylene glycol, neopentyl glycol, trimethylolpropane, and castor oil, i.e., adducts. These can be used alone or in combination of two or more. Among these, from the perspective of reactivity with hydroxyl groups, trimethylolpropane-modified aromatic polyisocyanates are preferred, trimethylolpropane-modified toluene diisocyanate and trimethylolpropane-modified xylylene diisocyanate are more preferred, and trimethylolpropane-modified toluene diisocyanate is further preferred.
[0192] The content of the isocyanate crosslinking agent in the adhesive composition is preferably 0.1 parts by mass or more, and more preferably 0.3 parts by mass or more, relative to 100 parts by mass of the (meth)acrylate polymer. In addition, the upper limit of the content is preferably 10 parts by mass or less, and is adjusted with reference to the adhesive force. By using an isocyanate crosslinking agent, the adhesion with the glass cloth layer can be improved, and undesirable conditions such as paste residue or peeling from the support during processing can be reduced.
[0193] (Additives, etc.)
[0194] In the range that does not hinder the purpose of the present invention, various additives commonly used in acrylic adhesives can be added to the adhesive composition. As various additives, for example, adhesion imparting agents, antioxidants, softeners, fillers, flame retardants can be listed. In addition, the polymerization solvent or dilution solvent described later is not included in the additives constituting the adhesive composition. The flame retardant is preferably an aluminum phosphate flame retardant.
[0195] [Method for producing insulating adhesive tape]
[0196] The method for manufacturing the insulating adhesive tape of this embodiment is not particularly limited. For example, Figure 1B In the case of the insulating adhesive tape 1 as shown, an adhesive composition is applied to a release film subjected to a peeling treatment and cured to obtain an adhesive layer, which is laminated on a glass cloth to produce a laminate a of an adhesive layer 13 having an adhesive non-impregnated layer 13a not impregnated in the glass cloth and an adhesive impregnated layer 13b impregnated in the glass cloth, and a glass cloth layer 11.
[0197] Then, an insulating composition is applied to the surface opposite to the surface provided with the adhesive layer 13 via the glass cloth layer 11 of the laminate a, and dried and cured, thereby producing a mold release film such as Figure 1B The insulating adhesive tape 1 includes an insulating layer 12 having an insulating non-impregnated layer 12a not impregnated in the glass cloth layer 11 and an insulating impregnated layer 12b impregnated in the glass cloth layer 11, an adhesive layer 13 having an adhesive impregnated layer 13b similarly impregnated in the glass cloth layer 11, and a glass cloth layer 11 between the insulating layer 12 and the adhesive layer 13. From the viewpoint of obtaining an insulating adhesive tape without voids, it is desirable to adopt a process of adjusting the viscosity of the insulating composition, directly applying the insulating composition to the glass cloth to impregnate it, and then drying it. The tape may be wound around a cylindrical core material together with a release film to form a roll, or the release film may be peeled off from the adhesive layer 13 as needed, and the adhesive layer 13 may be wound around a core material while being laminated so as to be in contact with the insulating layer 12 to form a roll.
[0198] Furthermore, the insulating composition is first applied to the release film and dried, and then the glass cloth is laminated and cured to obtain a laminate b of the insulating layer 12 and the glass cloth layer 11 having the insulating non-impregnated layer 12a and the insulating impregnated layer 12b, and then the adhesive composition is applied to the glass cloth, dried, and cured to produce an insulating adhesive tape having a release film on the side of the insulating layer 12. The tape may be laminated while being wound around a core material so that the adhesive layer 13 and the insulating layer 12 are in contact with each other, as required, by peeling the release film from the insulating layer 12.
[0199] In addition, from the viewpoint of improving the adhesion with the insulating composition or the adhesive composition and reducing voids during drying, the glass cloth may be used after being subjected to a surface treatment such as a primer treatment, a corona treatment, or a plasma treatment.
[0200] The coating liquid for the insulating layer and the adhesive layer may be applied by a conventional method, for example, bar coating, knife coating, Meyer bar coating, roll coating, blade coating, die coating, gravure coating, and dip coating.
[0201] Regarding the drying and curing conditions of the insulating composition, if the insulating composition contains urethane acrylate as the main component, it is preferably dried at 80°C to 150°C by removing the solvent, and then heated by a high-pressure mercury lamp at an intensity of 120 mW / cm 2 , cumulative light intensity 1000mJ / cm 2 If the insulating composition is mainly composed of polyimide and polyamide, it is preferably dried at 100°C to 200°C for 2 to 5 minutes by removing the solvent and hardening with a crosslinking agent. It is more preferably aged at room temperature to 50°C for 1 hour to 5 days after drying.
[0202] Regarding the drying and curing conditions in the adhesive composition, in the case of a silicone adhesive, whether it is a peroxide curing type or an addition curing type, it is preferred to perform drying and curing by removing the solvent in hot air at 120°C to 200°C for 5 minutes, and more preferably to further age at room temperature to about 50°C for about 1 hour to 5 days. In the case of an acrylic adhesive, it is preferred to perform drying and curing by removing the solvent in hot air at 80°C to 150°C for 1 minute to 5 minutes, and more preferably to further age at room temperature to about 50°C for about 1 hour to 5 days.
[0203] Examples of the films used for the release film include: polyester films formed from polyesters such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate; polyolefin films formed from polyolefins such as polyethylene, polypropylene, and polymethylpentene; polycarbonate films; plastic films such as polyvinyl acetate films; any of paper films such as pulp, or laminates formed from two or more of these material layers, and the like, and materials treated with a release agent on the above films can be used.
[0204] (Other layers)
[0205] In adopting Figure 1BIn the case of the product mode in which the insulating adhesive tape 1 is wound around a core material, the adhesive layer 13 is in direct contact with the insulating layer 12 as a surface layer. Therefore, a release agent may be applied to the surface of the insulating layer 12 as needed to form a release layer so that the interface between the insulating layer 12 and the adhesive layer 13 can be cleanly peeled off.
[0206] Examples of the release agent-imparting material used as a raw material of the release layer include silicone release agents, long-chain alkyl pendant polymer release agents in which a C16-24 alkyl group is arranged in a pendant state via an ester group or an ether group, and fluorine-based release agents.
[0207] <Other embodiments>
[0208] From the viewpoint of improving workability such as cutting or punching of the insulating adhesive tape in the present disclosure and improving the toughness (toughness) of the tape when attached to a target object, it is also preferred to use the insulating adhesive tape in a form having a thermoplastic resin layer.
[0209] The thermoplastic resin layer 14 is preferably Figure 4 The embodiment shown is located between the glass cloth layer 11 and the insulating layer 12 (embodiment 2), Figure 5 In order to improve the bonding strength between the thermoplastic resin layer 14 and the glass cloth layer 11 in the second embodiment, the adhesive layer 13 may be provided as shown in the third embodiment. Figure 6 As shown in FIG. 1 , an adhesive layer 15 is formed between the glass cloth layer 11 and the thermoplastic resin layer 14 (Embodiment 4).
[0210] In the third embodiment, in order to improve the bonding strength between the thermoplastic resin layer 14 and the glass cloth layer 11, Figure 7 As shown in FIG. 1 , an adhesive layer 15 is formed between the glass cloth layer 11 and the thermoplastic resin layer 14 (Embodiment 5).
[0211] Embodiments 2 and 3 can be formed, for example, by heating a thermoplastic resin film to a semi-molten state and laminating it with a glass cloth layer 11 to form a laminate of glass cloth layer 11 / thermoplastic resin layer 14 , and then laminating the insulating layer 12 and the adhesive layer 13 .
[0212] Embodiments 4 and 5 can be formed, for example, by forming an adhesive layer 15 on a thermoplastic resin layer 14, laminating a glass cloth layer 11, thereby forming a laminate of glass cloth layer 11 / adhesive layer 15 / thermoplastic resin layer 14, and then laminating the insulating layer 12 and the adhesive layer 13. In addition, it is also preferable that the adhesive layer 15 in Embodiment 5 is set as the adhesive layer 13.
[0213] The thickness of the thermoplastic resin layer 14 in Embodiments 2 to 5 is preferably 5 μm to 50 μm, and 10 μm to 30 μm is preferred because it can be formed without affecting the tracking resistance. The thickness of the adhesive layer 15 can be any thickness as long as the thermoplastic resin layer can be bonded to other layers, and is preferably 1 μm to 15 μm within a range that does not affect the tracking resistance.
[0214] The thermoplastic resin film in the thermoplastic resin layer 14 may be any thermoplastic resin that can be produced into a film, and any existing resin may be used. For example, polyethylene resin, polypropylene resin, polybutadiene resin, cyclic olefin resin, polymethylpentene resin, polystyrene resin, ethylene vinyl acetate copolymer, ethylene vinyl alcohol copolymer resin, ethylene acrylate copolymer, acrylonitrile-styrene resin, acrylonitrile-chlorinated polystyrene-styrene copolymer resin, acrylonitrile-acrylic rubber-styrene copolymer resin, acrylonitrile-butadiene-styrene copolymer resin, silicone resin, acetate resin, cellulose acetate resin, methacrylic resin, acrylic resin, vinyl chloride resin, chlorinated polyethylene resin, fluorinated polyethylene resin, polyvinylidene fluoride ... Vinylidene fluoride resin, nylon resin, polyacetal resin, polyester resin, polyethylene terephthalate resin, polyethylene naphthalate resin, polybutylene terephthalate resin, polycarbonate resin, modified polyphenylene ether resin, thermoplastic polyurethane elastomer, polyphenylene sulfide resin, polyetheretherketone resin, liquid crystal polymer, polytetrafluoroethylene resin, polyfluoroalkoxy resin, polyetherimide resin, polysulfone resin, polyketone resin, thermoplastic polyimide resin, polyamideimide resin, polyarylate resin, polysulfone resin, polyethersulfone resin, biodegradable resin, biomass resin, and refers to a resin formed by filming. A thermoplastic resin film formed by filming a polyethylene terephthalate resin having high smoothness and low cost can be particularly suitably used.
[0215] The adhesive used in the bonding layer 15 can be any adhesive as long as it can bond the thermoplastic resin layer 14 to other layers. Existing adhesives can be used, and examples include adhesives hardened from acrylic resins, polyester resins, epoxy resins, urethane resins, silicone resins, etc. Commercially available products include polyester adhesive TM-K76 (hardener CAT-RT85) manufactured by Toyo-Morton. The composition of the bonding layer 15 and the adhesive layer 13 may be the same or different.
[0216] The insulating layer 12 and the adhesive layer 13 in the second to fifth embodiments may be made of the same Figure 1A The same materials as described in the above.
[0217] The insulating adhesive tape disclosed herein may further include layers to impart functions (characteristics) corresponding to the purpose within the scope of not hindering the purpose of the present invention. For example, a heat dissipation layer, a water vapor barrier layer, an electromagnetic wave absorption layer, a design layer based on printing or coloring, and a polarizing layer may also be included as needed. Among them, even in the case described above, it is necessary to make the glass cloth impregnated with a hardened material of an insulating composition or a hardened material of an adhesive composition. In addition, within the scope of not hindering the purpose of the present invention, a protective layer such as a protective layer for protecting the surface of the insulating layer 12 may also be formed on the surface layer of the insulating layer 12.
[0218] Example
[0219] Hereinafter, the present disclosure will be described based on the embodiments. In addition, the present disclosure is not limited to the following embodiments, and the following embodiments may be deformed and changed based on the main idea of the present disclosure, and these are not excluded from the scope of the present disclosure. In addition, in the embodiments, "parts" are "parts by mass" and "%" are "% by mass". The amounts in the table are parts by mass.
[0220] [Raw materials for insulating composition]
[0221] <Acrylic materials>
[0222] (a-1) Urethane acrylate oligomer Mw: 2100, trifunctional containing EO chain
[0223] (a-2) Urethane acrylate oligomer Mw: 2000, trifunctional
[0224] (a-3) Urethane acrylate oligomer Mw: 1000, pentafunctional
[0225] (a-4) Urethane acrylate oligomer Mw: 300, difunctional
[0226] (a-5) Urethane acrylate oligomer Mw: 14000, difunctional
[0227] (a-6) Urethane acrylate oligomer Mw: 18000, difunctional
[0228] <Photopolymerization initiator>
[0229] Oligo{2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propanone
[0230] <Polyimide resin>
[0231] Cyclohexanone (773.5 g) was added to a four-necked flask including a stirrer, a reflux cooling tube with a Dean-Stark apparatus, a nitrogen inlet tube, and a thermometer while introducing nitrogen gas. Then, 534.3 g (1.00 mole) of DDA shown in Table 1 was added as a diamine while stirring. Furthermore, 117.58 g (0.524 mole) of TCA shown in Table 1 and 157.6 g (0.524 mole) of TDA were added as tetracarboxylic dianhydride, respectively, and stirred at room temperature for 30 minutes. The temperature was raised to 100°C, stirred for 3 hours, and then the oil bath was removed and returned to room temperature to obtain a varnish-like polyimide precursor. Thereafter, a Dean-Stark apparatus was used to remove the distilled water outside the system while heating at 170°C for 10 hours to perform imidization and obtain a polyimide resin solution. Cyclohexane was added to the obtained polyimide resin solution to adjust the nonvolatile content to 50%.
[0232] <Polyamide resin>
[0233] A polyamide resin solution was obtained by the same method as that for the polyimide resin except that the monomers described in Table 1 were used.
[0234] <Evaluation of polyimide resin and polyamide resin>
[0235] Table 1 shows the results of measuring the weight average molecular weight (Mw), aromatic ring concentration, and functional group concentration based on the type of terminal functional group of the polyimide resin and polyamide resin obtained in each synthesis example by the following measuring methods.
[0236] [Weight average molecular weight (Mw)]
[0237] The weight average molecular weight (Mw) is measured using a GPC (gel permeation chromatograph) "GPC-101" manufactured by Showa Denko (Co., Ltd.). GPC is a liquid chromatograph that separates and quantifies substances dissolved in a solvent (THF: tetrahydrofuran) according to the difference in their molecular sizes. The column is used by connecting two "KF-805L" (manufactured by Showa Denko: GPC column: 8mmID×300mm size) in series. The measurement is carried out under the conditions of a sample concentration of 1% by mass, a flow rate of 1.0mL / min, a pressure of 3.8MPa, and a column temperature of 40°C. The weight average molecular weight (Mw) is determined by polystyrene conversion. Data analysis is performed by using the manufacturer's built-in software to calculate the calibration curve, molecular weight, and peak area to obtain the weight average molecular weight (Mw).
[0238] [Aromatic ring concentration]
[0239] The aromatic ring concentration of the polyimide resin or polyamide resin can be determined by the above-mentioned formula (1).
[0240] [Functional group concentration (functional group value)]
[0241] (Acid value)
[0242] Accurately weigh about 1 g of sample in a co-stopped conical flask and add 100 mL of cyclohexanone solvent to dissolve it. Add phenolphthalein test solution as an indicator and keep it for 30 seconds. Then, titrate with 0.1N alcoholic potassium hydroxide solution until the solution turns light red. The acid value is calculated by formula (2) (unit: mgKOH / g).
[0243] Acid value (mgKOH / g) = (5.611×a×F) / S formula (2)
[0244] S, a, and F in the formula (2) represent the following.
[0245] S: Sample collection amount (g)
[0246] a: Consumption of 0.1N alcoholic potassium hydroxide solution (mL)
[0247] F: The potency of 0.1N alcoholic potassium hydroxide solution
[0248] (anhydride value)
[0249] Accurately weigh about 1g of the sample in a co-corked conical flask and add 100mL of 1,4-dioxane solvent to dissolve it. Add 10mL of a mixed solution of octylamine, 1,4-dioxane, and water (mixing ratio by mass is 1.49 / 800 / 80) that is larger than the amount of anhydride groups in the sample and stir for 15 minutes to react with the anhydride groups. Thereafter, the excess octylamine is titrated with a mixed solution of 0.02M perchloric acid and 1,4-dioxane. In addition, 10mL of a mixed solution of octylamine, 1,4-dioxane, and water (mixing ratio by mass is 1.49 / 800 / 80) without adding the sample is used as a blank and measured. The anhydride value is calculated by formula (3) (unit: mgKOH / g).
[0250] Acid anhydride value (mgKOH / g) = 0.02 × (BS) × F × 56.11 / W Formula (3)
[0251] B, S, W, and F in the formula (3) represent the following.
[0252] B: Blank titration (mL)
[0253] S: Titration of the sample (mL)
[0254] W: sample solid amount (g)
[0255] F: 0.02 mol / L perchloric acid titer
[0256] [Table 1]
[0257] Table 1
[0258]
[0259] <Production of Insulating Composition Z>
[0260] [Insulating composition Z-1]
[0261] 5.0 g of a photopolymerization initiator and 100 g of a diluent solvent of MEK:IPA (isopropyl alcohol) = 1:9 were mixed with 100 g of the urethane acrylate oligomer (a-1) to obtain an insulating composition Z-1.
[0262] [Insulating composition Z-2]
[0263] 5.0 g of a photopolymerization initiator and 100 g of a diluent solvent of MEK:IPA (isopropyl alcohol) = 1:9 were mixed with 100 g of the urethane acrylate oligomer (a-2) to obtain an insulating composition Z-2.
[0264] [Insulating composition Z-3]
[0265] 5.0 g of a photopolymerization initiator and 100 g of a dilution solvent of MEK:IPA (isopropyl alcohol) = 1:9 were mixed with 100 g of the urethane acrylate oligomer (a-3) to obtain an insulating composition Z-3.
[0266] [Insulating composition Z-4]
[0267] 5.0 g of a photopolymerization initiator and 100 g of a diluent solvent of MEK:IPA (isopropyl alcohol) = 1:9 were mixed with 100 g of the urethane acrylate oligomer (a-4) to obtain an insulating composition Z-4.
[0268] [Insulating composition Z-5]
[0269] 5.0 g of a photopolymerization initiator and 100 g of a dilution solvent of MEK:IPA (isopropyl alcohol) = 1:9 were mixed with 100 g of the urethane acrylate oligomer (a-5) to obtain an insulating composition Z-5.
[0270] [Insulating composition Z-6]
[0271] 5.0 g of a photopolymerization initiator and 100 g of a dilution solvent of MEK:IPA (isopropyl alcohol) = 1:9 were mixed with 100 g of the urethane acrylate oligomer (a-6) to obtain an insulating composition Z-6.
[0272] [Insulating composition Z-7]
[0273] In 167.8 g of the polyimide resin solution, 1.67 g of TETRAD C (epoxy compound (1,3-bis(N,N-diglycidylaminoethyl)cyclohexane, manufactured by Mitsubishi Gas Chemical Co., Ltd.)) as a crosslinking agent, 0.43 g of DBU (1,8-diazabicyclo[5,4,0]-undecene-7) as a catalyst, and 30.1 g of toluene as a solvent were mixed and stirred using a mixer to obtain an insulating composition Z-7.
[0274] [Insulating composition Z-8]
[0275] 1.67 g of TETRAD C as a crosslinking agent, 0.43 g of DBU as a catalyst, and 30.1 g of toluene as a solvent were mixed with 167.8 g of the polyamide resin solution, and the mixture was stirred with a mixer to obtain an insulating composition Z-8.
[0276] [Raw materials of adhesive composition]
[0277] <Synthesis of acrylic adhesive>
[0278] Into a four-necked flask including a stirrer, a reflux cooling tube, a nitrogen inlet tube, and a thermometer, 500 g of ethyl acetate was heated in a water bath while introducing nitrogen gas. Then, a mixture obtained by adding 240 g of BA (n-butyl acrylate), 240 g of 2-EHA (2-ethylhexyl acrylate), 20 g of AA (acrylic acid), and 0.5 g of AIBN (azobisisobutyronitrile) as an initiator was added dropwise to the ethyl acetate, and the mixture was reacted for 8 hours while maintaining reflux. After the reaction, 110 g of ethyl acetate was added to obtain an acrylic adhesive having a non-volatile content of 45% and a weight average molecular weight (Mw) of 650,000.
[0279] The weight average molecular weight (Mw) is measured under the following conditions: The weight average molecular weight (Mw) is determined by a calibration curve method using polystyrene having a known weight average molecular weight as a standard substance.
[0280] · Device name: LC-GPC system "Prominence" manufactured by Shimadzu Corporation
[0281] Column: TSKgel (registered trademark) α-M manufactured by Tosoh Corporation, 2 connected in series
[0282] Mobile phase solvent: tetrahydrofuran
[0283] Flow rate: 1.0mL / min
[0284] Column temperature: 40℃
[0285] <Production of Adhesive Composition N>
[0286] [Adhesive composition N-1]
[0287] 0.5 g of an isocyanate curing agent (Duranate TLA-100 manufactured by Asahi Chemical Industry Co., Ltd., NCO wt%: 23.3%) as a cross-linking agent was added to 100 g of the acrylic adhesive obtained above, and the mixture was stirred and mixed to obtain an adhesive composition N-1.
[0288] [Adhesive composition N-2]
[0289] As the silicone adhesive: 100 g of KR-130 (manufactured by Shin-Etsu Chemical Co., Ltd.), 0.5 g of benzoyl oxide and 50 g of MEK were mixed and stirred to obtain an adhesive composition N-2.
[0290] <Properties of glass cloth>
[0291] Table 2 shows the properties of glass cloth G-1 to glass cloth G-6, which are raw materials of the glass cloth layers used in Examples.
[0292] [Table 2]
[0293] Table 2
[0294]
[0295] <Other materials>
[0296] Release film: SP PET-01-BU, thickness 50 μm, one-side silicone release treatment, PET film separator manufactured by Mitsui Chemicals Tohcello Co., Ltd.
[0297] [Resin film]
[0298] PI: Aromatic polyimide film (manufactured by Toray Dupont Co., Ltd., product name: Kapton 100H).
[0299] ·PEN: Polyethylene naphthalate film (manufactured by Toyobo Co., Ltd., product name: Teonex Q51-25)
[0300] GSF: A resin film containing glass fiber filler; 100 g of the insulating composition Z-7 and 10 g of a glass fiber filler (milled fiber HP3610, glass filament diameter 10 μm) were mixed, applied on a release film to a thickness of 30 μm after drying, dried at 150° C., and the release film was removed.
[0301] <Manufacturing of insulating adhesive tape>
[0302] [Example 1]
[0303] The adhesive composition N-1 was applied to the release treated surface of the 300 mm square release film by a doctor blade to a thickness of 30 μm after drying, and dried in an oven at 100° C. for 5 minutes to obtain an adhesive layer. The adhesive layer and the glass cloth G-1 were bonded and integrated by a laminator at a roll pressure of 0.2 MPa, a speed of 100 mm / min, and a temperature of 23° C. to obtain a laminate a having an adhesive layer 13 / glass cloth layer 11 on a release film (a layer thickness of 50 μm with an adhesive impregnated layer of 5 μm and an adhesive non-impregnated layer of 25 μm).
[0304] Next, the insulating composition Z-1 was applied to the glass cloth layer 11 surface opposite to the adhesive layer 13 of the laminate a using a doctor blade so that the total thickness of the insulating adhesive tape became 60 μm, and after hot air drying at 100° C. for 3 minutes, the insulating composition Z-1 was irradiated with a high-pressure mercury lamp at an intensity of 80 mW / cm 2 , cumulative light intensity 500mJ / cm 2 The insulating adhesive tape of Example 1 was obtained by curing.
[0305] A portion of the insulating adhesive tape ZN-1 was frozen with liquid nitrogen and cut with a razor to obtain a tape cross section. The thickness of each layer was measured by SEM observation of the cross section at a magnification of 500.
[0306] [Example 2 to Example 6, Example 9 to Example 23]
[0307] Insulating adhesive tapes according to Examples 2 to 6 and Examples 9 to 23 were obtained by the same method as in Example 1 except that the raw materials of the insulating layer were changed to those shown in Tables 3 to 6.
[0308] [Example 7 to Example 8]
[0309] Insulating adhesive tapes of Examples 7 and 8 were obtained by the same method as in Example 1, except that the raw materials or thickness of each layer were changed to those shown in Tables 3 to 6, the drying temperature of the insulating composition was changed to 150° C., and the ultraviolet irradiation with a mercury lamp was not performed.
[0310] [Comparative Example 1]
[0311] The laminated body a obtained in the production process of Example 1 is referred to as Comparative Example 1.
[0312] [Comparative Example 2]
[0313] An insulating adhesive tape of Comparative Example 2 was obtained by the same method as in Example 1, except that the insulating layer was directly coated on the surface of the adhesive layer 13 instead of laminating the glass cloth layer after the adhesive layer 13 was prepared.
[0314] [Comparative Examples 3 to 5]
[0315] Insulating adhesive tapes of Comparative Examples 3 and 4 were obtained by the same method as in Example 1 except that a resin film PI, PEN or GSF was laminated to the adhesive layer instead of glass cloth and an insulating layer was applied to the resin film surface opposite to the surface in contact with the adhesive layer.
[0316] The thicknesses were measured by cutting out a cross section by the ion milling method and observing the cross section by SEM at a magnification of 500, and the average value of the five sections was taken.
[0317] <Evaluation of Insulating Adhesive Tape>
[0318] The various performance evaluation methods and evaluation criteria of the belts obtained in the respective Examples and Comparative Examples are shown below. The evaluation results based on the following evaluation criteria are shown in Tables 3 to 6.
[0319] [Tracking resistance]
[0320] As a method for measuring the tracking resistance of insulating materials, there is a proof tracking index (Proof Tracking Index) based on IEC60112, JISC2134, ASTM D3638 or Underwriters Laboratories (UL) 746A. The upper limit of the test voltage of PTI is specified as 600V. As a method for measuring the tracking performance using a high voltage exceeding 600V, there is an inclined plane tracking test (Inclined-Plane Tracking, IPT) based on IEC60587, JIS C2136 or ASTM D2303. The lower limit of the test voltage of IPT is specified as 1kV (1000V). In the CTI evaluation implemented at a test starting voltage of 300 volts after the revision of UL746A, since it is impossible to confirm the presence or absence of the reverse trend phenomenon, in this specification, according to IEC60112, the upper limit of the test voltage is set to 1000V for testing, and the PTI under the following specified voltage is measured. The specified voltage is set to 300V, 600V, and 1000V.
[0321] In this specification, when there is flash, a separate criterion is set independently of the case where there is flash, and it is evaluated as the presence of the reverse tendency phenomenon. The PTI of the insulating adhesive tape and the presence of the reverse tendency phenomenon are evaluated based on the following evaluation criteria.
[0322] (Evaluation Criteria)
[0323] S: Passed the test at all specified voltages.
[0324] A: The test passed at the specified voltage of 600V and 300V, but did not reach 1000V.
[0325] B: The test was passed at the specified voltage of 600V and 300V, but did not reach 1000V. There was flash at the specified voltage of 300V (with a reverse trend).
[0326] C: The test was passed at the specified voltage of 600V, but did not reach 300V or 1000V (there was a reverse trend).
[0327] [Heat resistance]
[0328] In accordance with JIS C4003:2010, a test for thermal evaluation of the insulating adhesive tape after the release film was peeled off was performed to measure the heat resistance temperature, and the heat resistance of the insulating adhesive tape was evaluated based on the following evaluation criteria.
[0329] (Evaluation Criteria)
[0330] S: Heat-resistant temperature is 200°C or higher (heat-resistant class: N, R).
[0331] A: Heat resistance temperature is 180°C or higher and lower than 200°C (heat resistance class: H).
[0332] B: Heat resistance temperature is 155°C or higher and lower than 180°C (heat resistance class: F).
[0333] C: Heat-resistant temperature is less than 155°C (heat-resistant grade: B or less).
[0334] [Insulation]
[0335] Prepare 3 pieces of 25 mm square insulating adhesive tapes, and measure the insulation breakdown voltage of each piece once using an AC withstand voltage tester (7470 manufactured by Measurement Technology Research Institute Co., Ltd.) in accordance with JIS C 2110. The measurement was performed at a frequency of 60 Hz and a voltage increase rate of 0.1 kV / sec under an environment of 23°C and 50% RH, and the average value of the absolute values measured 3 times for each tape was set as the insulation breakdown voltage (kV).
[0336] In addition, the measurement is performed by attaching the adhesive layer after the release film is peeled off to the lower electrode of the base as the electrode, and sandwiching one piece in a manner where the upper electrode and the insulating layer are in contact. S is good, A is generally usable, B is usable according to the use environment, and C is evaluated as impractical as an insulating adhesive tape.
[0337] S: 5kV or above.
[0338] A: 4kV or more and less than 5kV.
[0339] B: 3kV or more and less than 4kV.
[0340] C: Less than 3kV.
[0341] [Winding processability]
[0342] Each insulating adhesive tape was cut into a strip with a width of 2 cm and a length of 20 cm, and the insulating adhesive tape was wound in a direction perpendicular to the length direction on a steel round rod with a length of 5 cm and an outer diameter of 2 mm. As for the winding, the stripping film was peeled off so that the exposed adhesive layer was attached to the steel rod. After winding for one round, the insulating adhesive tape was overlapped and wound in an opposite manner to the adhesive layer until the end of the tape. The steel rod with the tape wound was fixed upright on a fixture and left to stand for 1 day in an environment of 23°C and 50%RH for 1 hour to stabilize the close contact of the adhesive tape, and 4 test samples were prepared.
[0343] Each test sample was exposed to the following four environmental conditions, and the peeling of the tape end was evaluated according to the following evaluation criteria. In addition, the peeling of the end was considered to be present when the tape end contacted by the adhesive surface before the test was peeled off by more than 1 mm.
[0344] Condition 1: Stand at 100°C for 1 hour.
[0345] Condition 2: Stand at 200°C for 1 hour.
[0346] Condition 3: After standing at 100°C for 30 minutes, standing at -10°C for 30 minutes, the operation was repeated 5 times.
[0347] Condition 4: After standing at 200° C. for 30 minutes, the sample was allowed to stand at −10° C. for 30 minutes, and the above operation was repeated 5 times.
[0348] (Evaluation Criteria)
[0349] S: No end peeling was observed under all conditions. Best.
[0350] A: No peeling under conditions 1, 2, and 3, but peeling was observed under condition 4. Good.
[0351] B: No peeling under conditions 1 and 3, but peeling was observed under conditions 2 and 4. Can be used for a long time in general use environments.
[0352] C: No peeling under conditions 1 and 2, but peeling was observed under conditions 3 and 4. Can be used in general environments for a short period of time.
[0353] D: No peeling under condition 1, but peeling was observed under conditions 2, 3, and 4. Or the shape cannot be maintained. The usage environment is limited.
[0354] [Table 3]
[0355] Table 3
[0356]
[0357] [Table 4] Table 4
[0358]
[0359] [Table 5] Table 5
[0360]
[0361] [Table 6]
[0362] Table 6
[0363]
[0364] In Examples 1 to 23, the reverse tendency phenomenon was overcome by combining a specific glass cloth layer, a specific insulating layer, and a specific adhesive layer, and the tracking resistance, insulation, winding processability, and heat resistance were achieved at a high level. In addition, by being in the preferred range, further improvement in performance can be seen, and in some insulating adhesive tapes, high processability is achieved while having PTI: 1000V, unparalleled tracking resistance, and high heat resistance.
[0365] On the other hand, in Comparative Example 1, since there is no insulating layer, the tracking resistance and insulation are insufficient. In Comparative Example 2, since there is no glass cloth layer, the heat resistance and winding processability are insufficient. In Comparative Examples 3 and 4, since there is no glass cloth layer, the tracking resistance and heat resistance including the reverse trend phenomenon are insufficient. In Comparative Example 5 in which glass fiber filler is used instead of glass cloth, the heat resistance and winding processability are insufficient.
[0366] This application claims the benefit of priority based on Japanese patent application No. 2022-79139 filed on May 13, 2022 and Japanese patent application No. 2022-124432 filed on August 4, 2022, the disclosures of which are hereby incorporated by reference in their entirety into this application.
[0367] Explanation of symbols
[0368] 1 Insulation adhesive tape
[0369] 11 Glass cloth layer
[0370] 12 Insulation layer
[0371] 12a Insulation non-impregnated layer
[0372] 12b Insulation impregnation layer
[0373] 13 Adhesive layer
[0374] 13a Adhesive non-impregnated layer
[0375] 13b Adhesive impregnation layer
[0376] 14 Thermoplastic resin layer
[0377] 15 Adhesive layer
Claims
1. An insulating adhesive tape comprising an insulating layer, an adhesive layer, and a glass cloth layer, The glass cloth layer is located between the insulating layer and the adhesive layer, and The glass cloth layer is impregnated with at least one of the insulating layer and the adhesive layer. 2 . The insulating adhesive tape according to claim 1 , wherein a thickness of the insulating adhesive tape is 30 μm to 200 μm. 3 . The insulating adhesive tape according to claim 1 , wherein the glass cloth layer has a thickness of 10 μm to 50 μm and a weaving density of 10 to 50 strands / 10 mm. 4 . The insulating adhesive tape according to claim 1 , wherein the diameter of the glass filaments constituting the glass cloth layer is 100 μm to 500 μm.
5. The insulating adhesive tape according to claim 1, characterized in that: The insulating layer is a hardened material formed by active energy rays.
6. The insulating adhesive tape according to claim 1, characterized in that: The insulating layer is a layer formed by curing an acrylic material having a weight average molecular weight of 300 to 15,000.
7. The insulating adhesive tape according to claim 1, characterized in that: The insulating layer is formed of a resin mainly composed of polyimide or polyamide having an aromatic ring concentration of 30 mass % or less.
8. The insulating adhesive tape according to claim 1, further comprising a thermoplastic resin layer. The thermoplastic resin layer is located between the glass cloth layer and the insulating layer, or between the glass cloth layer and the adhesive layer.
9. The insulating adhesive tape according to any one of claims 1 to 8, wherein the tracking index (PTI) measured by a test based on IEC 60112, JIS C2134 or ASTM D3638 is 300 V and 600 V.
10. The insulating adhesive tape according to any one of claims 1 to 8, wherein a tracking index (PTI) measured by a test based on IEC 60112, JIS C2134 or ASTM D3638 is 300 V, 600 V and 1000 V.
